Flexible image display device constitution member adhesive layer, laminate, and image display device
Patent Information
- Application Number
- CN202580021714.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-21
- Publication Date
- 2026-10-20
AI Technical Summary
[0007]此外,由于反复进行折叠操作,存在粘合层剥离的可能性,除此以外,还存在由于对作为被粘物的构件施加应力而构件产生裂纹或者断裂的可能性,因此也要求是特别是相对于作为严酷条件的低温下的反复折叠操作具有耐久性的层叠片
[0048]根据本发明,能提供弯曲适应性优异并且凝聚力和/或粘接力良好的柔性图像显示装置构成构件用粘合层、层叠体以及图像显示装置。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to adhesive layers, laminates, and image display devices for the components of flexible image display devices. Background Technology
[0002] In recent years, in order to improve the visual verifiability of image display devices, adhesive layers and adhesives have been used to fill the gaps between image display panels such as LCD (Liquid Crystal Display), PDP (Plasma Display Panel), or EL (Electro-Luminescence) and the protective panel and touch panel components disposed on their front side (visual verifiability side). This suppresses diffuse reflection that would occur if the gaps were not filled, i.e., diffuse reflection of incident light and outgoing light from the displayed image at the air layer interface.
[0003] At this time, for example, when the protective panel is made of plastic, gas is sometimes generated from the protective panel (called degassing). Therefore, if the adhesive layer or adhesive does not have the adhesive and cohesive force to resist the gas pressure, the gas will remain in the adhesive layer or adhesive. If it becomes high temperature, the residual gas will foam and reduce the visual clarity of the image.
[0004] In addition, flexible displays, which can be bent freely, have recently attracted attention as the next generation of displays. Flexible displays mainly use organic electroluminescent (organic EL) displays.
[0005] In such an image display device, multiple component sheets such as surface protective film, cover lens, circular polarizer, touch film sensor, and light-emitting element are formed into a stacked structure by bonding with a transparent adhesive layer. Each stacked structure can be regarded as a stacked sheet formed by stacking component sheets and adhesive layer.
[0006] Bending display devices generate various problems caused by interlayer stress during bending. For example, there is a requirement for laminates to quickly return to a flat state without leaving any residual effects from being in a bent state when the screen is unfolded from a folded state.
[0007] Furthermore, due to repeated folding operations, there is a possibility of adhesive layer peeling. In addition, there is a possibility of component cracking or breaking due to stress applied to the component as the adhered object. Therefore, it is also required that the laminate be durable, especially relative to repeated folding operations at low temperatures as harsh conditions.
[0008] For the adhesive layer in such a flexible image display device, optical properties are a given, but flexibility, especially high durability against bending, is also required.
[0009] In addition to low-temperature durability, it is also required to suppress the phenomenon of adhesive layer overflow at high temperatures and to suppress the deformation of adhesive layer and the residue when bent in high-temperature environment. From these points of view, it is also required to have a high elastic modulus.
[0010] For example, Patent Document 1 discloses a laminated film with an adhesive layer that does not produce disorder in the image displayed on the folded portion after repeated bending.
[0011] In addition, Patent Document 2 discloses a laminate that aims to suppress peeling and other issues even through bending tests that closely approximate actual use conditions. This laminate has a double-sided adhesive sheet and a flexible component for an image display device. The double-sided adhesive sheet has a glass transition temperature and storage modulus within a specified range.
[0012] Existing technical documents
[0013] Patent documents
[0014] Patent Document 1: Japanese Patent Application Publication No. 2020-196255
[0015] Patent Document 2: International Publication No. 2018 / 173896 Summary of the Invention
[0016] The problem that the invention aims to solve
[0017] In Patent Documents 1 and 2, in order to impart sufficient flexibility to the cured resin composition at low temperatures and obtain folding resistance at low temperatures, a basic polymer with a low glass transition temperature is used, thereby enabling the adhesive sheet to have bending resistance at both high and low temperatures.
[0018] However, when using polymers with low glass transition temperatures, there is a tendency for insufficient adhesive and cohesive strength.
[0019] Therefore, in this context, the object of the present invention is to provide an adhesive layer, a laminate, and an image display device for use as constituent components of a flexible image display device, which have excellent bending adaptability and good cohesion and / or adhesion.
[0020] Solution for solving the problem
[0021] That is, the present invention has the following solution.
[0022] [1] An adhesive layer for a component of a flexible image display device, which satisfies the following necessary conditions [I] to [V],
[0023] The adhesive layer for the components of the flexible image display device is formed from a resin composition comprising a polymer (A), a crosslinking agent (B), and a polymerization initiator (C).
[0024] The polymer (A) comprises a copolymer formed of a monomeric component comprising at least 50% by mass of a compound containing a (meth)acryloyl group.
[0025] The crosslinking agent (B) comprises a crosslinking agent with three or more functional groups.
[0026] The polymerization initiator (C) comprises a pyrolysis-type photopolymerization initiator.
[0027] [I] The shear storage modulus (G'(-20℃)) at -20℃ is below 300kPa.
[0028] [II] The shear storage modulus (G'(85℃)) at 85℃ is above 5.0 kPa and below 30 kPa.
[0029] [III] The gel fraction is 45% or more and 95% or less.
[0030] [IV] The adhesion strength relative to the polyethylene terephthalate substrate is 5.0 N / cm or more at 23°C.
[0031] [V] Based on the maximum strain (γ) after applying a pressure of 10 kPa for 600 seconds with a thickness of 0.5–1.2 mm at 25°C. max(25) ) and then the strain (γ) after stress relief and 600 seconds. min(25) The recovery rate calculated using the following formula is over 70%.
[0032] Recovery rate (%) = [(γ)] max(25) -γ min(25) ) / γ max(25) ]×100
[0033] [2] An adhesive layer for constituting components of the flexible image display device according to [1], wherein,
[0034] The adhesive layer used for the components of the flexible image display device has an adhesion force of 4.5 N / cm or more relative to the glass substrate at 23°C.
[0035] [3] An adhesive layer for constituting components of the flexible image display device according to [1] or [2], wherein,
[0036] The flexible image display device uses an adhesive layer with a thickness of 0.5–1.2 mm. The maximum strain (γ) after applying a pressure of 10 kPa for 600 seconds at 25°C is measured. max(25) The percentage is below 600%.
[0037] [4] An adhesive layer for constituting a flexible image display device according to any one of [1] to [3], wherein,
[0038] The glass transition temperature (Tg) of the adhesive layer used to construct the flexible image display device, defined by the maximum value of Tanδ obtained through dynamic viscoelasticity measurement in shear mode at a frequency of 1 Hz, is below -15°C.
[0039] [5] An adhesive layer for a flexible image display device constituent component with release film, the adhesive layer for a flexible image display device constituent component having one or more release films and a laminated structure of an adhesive layer for a flexible image display device constituent component according to any one of [1] to [4].
[0040] [6] A laminate comprising one or more components for an image display device and an adhesive layer for constituting a flexible image display device according to any one of [1] to [4].
[0041] [7] A laminate comprising two image display device constituent members and an adhesive layer for a flexible image display device constituent member disposed between the two image display device constituent members according to any one of [1] to [4].
[0042] [8] According to the laminate described in [7], wherein,
[0043] One of the components of the two image display devices is a surface protection panel, and the other is a component consisting of any one or any combination of two or more of the following: a touch sensor film, an image display panel, a color filter, a polarizing element, and a phase difference film.
[0044] [9] An image display device comprising a laminate according to any one of [6] to [8].
[0045]
[10] The image display device according to [9], wherein,
[0046] The image display device is a flexible image display device.
[0047] Invention Effects
[0048] According to the present invention, an adhesive layer, a laminate, and an image display device are provided as components for flexible image display devices, which have excellent bending adaptability and good cohesion and / or adhesion. Detailed Implementation
[0049] Hereinafter, an example of an embodiment of the present invention will be described in detail. However, the present invention is not limited to the embodiment described below.
[0050] It should be noted that, in this invention, the term "layer" conceptually includes sheets, films, and strips.
[0051] Furthermore, when referred to as "panel" in terms of things like image display panel or protective panel, it includes the plate, sheet, and film.
[0052] In this specification, when referred to as "x~y" (where x and y are arbitrary numbers), unless otherwise specified, it includes the meaning of "more than x and less than y", and also includes the meaning of "preferably greater than x" or "preferably less than y".
[0053] Furthermore, when it is recorded as "x or more" (where x is any number), unless otherwise specified, it includes the meaning of "preferably greater than x". When it is recorded as "y or less" (where y is any number), unless otherwise specified, it also includes the meaning of "preferably less than y".
[0054] Furthermore, "X and / or y (x and y can be any combination)" refers to at least one of x and y, specifically x only, y only, or x and y.
[0055] Furthermore, in this specification, "(meth)acrylic acid" means that it includes acrylic acid and methacrylic acid, "(meth)acrylate" means that it includes acrylate and methacrylate, and "(meth)acryloyl" means that it includes acryloyl and methacryloyl.
[0056] Regarding the numerical ranges described in this specification in stages, the upper or lower limit of a numerical range for a certain stage can be arbitrarily combined with the upper or lower limit of numerical ranges for other stages. Furthermore, the upper or lower limit of the numerical range described in this specification can also be replaced with the values shown in the embodiments.
[0057] Furthermore, in this specification, the main component refers to the component that has a significant impact on the properties of the material, and the content of this component is usually 50% or more by mass of the whole material, preferably 70% or more by mass, and particularly preferably 90% or more by mass.
[0058] <<Adhesive Layer>>
[0059] In one embodiment, the present invention is an adhesive layer for a flexible image display device component that satisfies the following necessary conditions [I] to [V] (hereinafter, the adhesive layer for a flexible image display device component of the embodiment is sometimes referred to as "this adhesive layer"). This adhesive layer is formed from a resin composition comprising a polymer (A), a crosslinking agent (B), and a polymerization initiator (C).
[0060] The polymer (A) comprises a copolymer in which more than 50% by mass of the monomer component is formed from a compound containing a (meth)acryloyl group.
[0061] The crosslinking agent (B) comprises a crosslinking agent with three or more functional groups.
[0062] The polymerization initiator (C) comprises a pyrolysis-type photopolymerization initiator.
[0063] [I] The shear storage modulus (G'(-20℃)) at -20℃ is below 300kPa.
[0064] [II] The shear storage modulus (G'(85℃)) at 85℃ is above 5.0 kPa and below 30 kPa.
[0065] [III] The gel fraction is 45% or more and 95% or less.
[0066] [IV] The adhesion strength relative to the polyethylene terephthalate substrate is 5.0 N / cm or more at 23°C.
[0067] [V] Based on the maximum strain (γ) after applying a pressure of 10 kPa for 600 seconds with a thickness of 0.5–1.2 mm at 25°C. max(25) ) and then the strain (γ) after stress relief and 600 seconds. min(25) The recovery rate calculated using the following formula is over 70%.
[0068] Recovery rate (%) = [(γ)] max(25) -γ min(25) ) / γ max(25) ]×100
[0069] The resin composition forming this adhesive layer is described in detail below.
[0070] <Resin Composition>
[0071] As described above, the resin composition comprises a polymer (A), a crosslinking agent (B), and a polymerization initiator (C). Furthermore, in this invention, "polymer (A)" also includes the concept of a prepolymer. It should be noted that the "prepolymer" refers to a substance obtained by partially polymerizing the copolymer components described later, and is a mixture of the polymer and unpolymerized copolymer components.
[0072] [Polymer (A)]
[0073] As the polymer (A), examples include copolymers in which 50% by mass or more of the monomer components are compounds having (meth)acryloyl groups, such as acrylic copolymers obtained by polymerizing alkyl (meth)acrylates and monomer components that can copolymerize with them. Preferably, the polymer (A) comprises structural sites derived from alkyl (meth)acrylates and structural sites derived from hydroxyl-containing (meth)acrylates. From the perspective of adhesive properties, acrylic copolymers comprising structural sites of alkyl (meth)acrylates (a1) (hereinafter sometimes referred to as "alkyl (meth)acrylate (a1)") with 3 or more carbon atoms derived from alkyl groups and structural sites derived from hydroxyl-containing (meth)acrylates (a2) are particularly preferred. Such acrylic copolymers are obtained by polymerizing a copolymer component comprising alkyl (meth)acrylate (a1) and hydroxyl-containing (meth)acrylate (a2).
[0074] In addition, the copolymer may also contain components other than alkyl (meth)acrylate (a1) and hydroxyl-containing (meth)acrylate (a2), such as at least one comonomer (a3) selected from alkyl (meth)acrylates and vinyl ester monomers having 1 or 2 carbon atoms in the alkyl group, olefinic unsaturated monomers (a4), other comonomers (a5), etc.
[0075] Furthermore, the polymer (A) typically contains 50% by mass or more of an acrylic copolymer, preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. There is no particular upper limit, and it can also be 100% by mass. Furthermore, the range of its content is, for example, 50 to 100% by mass.
[0076] [(Meth)acrylate (a1)]
[0077] Examples of the alkyl methacrylates (a1) include aliphatic methacrylates such as straight-chain alkyl methacrylates and branched-chain alkyl methacrylates, as well as alicyclic methacrylates.
[0078] Examples of aliphatic (meth)acrylates include: n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, lauryl (meth)acrylate, n-tridecyl (meth)acrylate, stearyl (meth)acrylate, eicosyl (meth)acrylate, and dodecyl (meth)acrylate. (Meth)acrylate behenate and other linear alkyl esters of (meth)acrylate; (meth)acrylate isopropyl ester, (meth)acrylate isobutyl ester, (meth)acrylate sec-butyl ester, (meth)acrylate tert-butyl ester, (meth)acrylate isoamyl ester, (meth)acrylate neopentyl ester, (meth)acrylate 2-ethylhexyl ester, (meth)acrylate isooctyl ester, (meth)acrylate isononyl ester, (meth)acrylate isodecanyl ester, (meth)acrylate isostearyl ester, (meth)acrylate isoeicosyl ester and other branched alkyl esters of (meth)acrylate.
[0079] Examples of alicyclic (meth)acrylates include: cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, adamantyl (meth)acrylate, and other alicyclic (meth)acrylates.
[0080] These can be used individually or in combination of two or more.
[0081] Among these, straight-chain alkyl esters of (meth)acrylate are preferred from the perspective of adhesion and resilience. Furthermore, from the viewpoint of achieving a balance between adhesion and flexibility at low temperatures, straight-chain alkyl esters and branched alkyl esters of (meth)acrylate with 3 or more but less than 18, more preferably less than 16, particularly less than 12, and especially less than 8 carbon atoms are preferred. Examples include n-propyl methacrylate, n-butyl methacrylate, n-pentyl methacrylate, n-hexyl methacrylate, n-octyl methacrylate, n-nonyl methacrylate, decyl methacrylate, and 2-ethylhexyl methacrylate. Among these, n-butyl methacrylate and 2-ethylhexyl methacrylate are preferred.
[0082] From the viewpoint of reducing the refractive index, alkyl (meth)acrylates with 4 or more carbon atoms, particularly 6 or more, especially 8 or more and 18 or less, particularly 16 or less, especially 12 or less are preferred.
[0083] Furthermore, from the viewpoint of improving flexural properties by suppressing the increase of shear storage modulus (G') at low temperatures, alkyl (meth)acrylates (a1) are particularly preferred.
[0084] From the viewpoint of suppressing the increase of shear storage modulus (G') at low temperatures, the content of the structural portion derived from alkyl methacrylate (a1) in polymer (A) is typically 50% by mass or more, preferably 60% by mass or more, particularly preferably 70% by mass or more, and typically 99% by mass or less, preferably 97% by mass or less, particularly preferably 95% by mass or less, with a range of content such as 50 to 99% by mass. If the content of the structural portion derived from alkyl methacrylate (a1) is above the aforementioned lower limit, there is a tendency to suppress the increase of shear storage modulus (G') at low temperatures; if it is below the upper limit, there is a tendency to balance other physical properties such as adhesion.
[0085] Furthermore, when using both linear alkyl methacrylate and branched alkyl methacrylate, the mass ratio [linear alkyl methacrylate / branched alkyl methacrylate] is typically 1 / 99 or more, preferably 50 / 50 or more, more preferably 65 / 35 or more, and typically 99 / 1 or less, preferably 95 / 5 or less, more preferably 90 / 10 or less. A range of mass ratios is, for example, 1 / 99 to 99 / 1. When the mass ratio of linear alkyl methacrylate to branched alkyl methacrylate is within the aforementioned range, there is a tendency for excellent adhesive strength when forming an adhesive.
[0086] [Contains hydroxy (meth)acrylates (a2)]
[0087] Examples of hydroxyl-containing (meth)acrylates (a2) include: 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, and other hydroxyalkyl (meth)acrylates; caprolactone-modified 2-hydroxyethyl (meth)acrylate and other caprolactone-modified hydroxy (meth)acrylates; diethylene glycol (meth)acrylate; polyethylene glycol (meth)acrylate; and polypropylene glycol (meth)acrylate. Methacrylates containing an oxyalkylene glycol structure, such as polytetramethylene glycol (meth)acrylate and polyoxyethylene polyoxypropylene glycol (meth)acrylate; methacrylates containing primary hydroxyl groups, such as 2-acryloyloxyethyl-2-hydroxyethyl phthalic acid; methacrylates containing secondary hydroxyl groups, such as 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, and 3-chloro-2-hydroxypropyl methacrylate; and methacrylates containing tertiary hydroxyl groups, such as 2,2-dimethyl-2-hydroxyethyl methacrylate. These can be used alone or in combination of two or more.
[0088] From the viewpoint of reducing the shear storage modulus (G') at low temperatures, hydroxyl-containing (meth)acrylates having hydroxyalkyl groups having 1 or more, more preferably 2 or more and 10 or less, more preferably 6 or less, especially 4 or less, carbon atoms are preferred. Examples include 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxypropyl (meth)acrylate. Primary hydroxyl-containing (meth)acrylates are particularly preferred, such as 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate.
[0089] Furthermore, when 2-hydroxyethyl methacrylate and 4-hydroxybutyl methacrylate are used as hydroxy(meth)acrylates (a2), the ratio [2-hydroxyethyl methacrylate / 4-hydroxybutyl methacrylate] is typically 30 / 70 or more by mass, preferably 40 / 60 or more, particularly preferably 45 / 55 or more, especially preferably 50 / 50 or more, and typically 95 / 5 or less, preferably 80 / 20 or less, particularly preferably 75 / 25 or less, especially preferably 70 / 30 or less, with a range of ratios such as 30 / 70 to 95 / 5. If 2-hydroxyethyl methacrylate is at or above the lower limit, there is a tendency for excellent adhesive strength when used to make an adhesive; if it is below the upper limit, there is a tendency for excellent flexural durability when used to make an adhesive.
[0090] It should be noted that, as the hydroxyl (meth)acrylate (a2), the lower the proportion of di(meth)acrylate contained in the hydroxyl (meth)acrylate (a2) in the form of impurities, the better. Specifically, it is preferred to use a substance of 0.5% by mass or less, particularly preferred to use a substance of 0.2% by mass or less, and even more preferred to use a substance of 0.1% by mass or less.
[0091] The content of the structural site derived from the hydroxyl-containing (meth)acrylate (a2) relative to the polymer (A) is generally 5% by mass or more, preferably 8% by mass or more, more preferably 10% by mass or more, further preferably 11% by mass or more, particularly preferably 12% by mass or more, and is generally 60% by mass or less, preferably 45% by mass or less, more preferably 35% by mass or less, further preferably 30% by mass or less, particularly preferably 25% by mass or less, and the range of its content is, for example, 5% to 45% by mass.
[0092] If the content of the structural part derived from hydroxyl (meth)acrylate (a2) is above the lower limit, there is a tendency for the adhesive layer to have excellent resistance to damp heat; if it is below the upper limit, there is a tendency for the heat resistance to be improved by suppressing unintentional self-crosslinking reactions.
[0093] [Comonomer (a3)]
[0094] In this invention, from the viewpoint of improving cohesion and thus the adhesive strength when the adhesive is made, it is preferable to also contain a copolymer (a3) as a copolymer component.
[0095] Examples of the comonomers (a3) include methyl methacrylate, ethyl methacrylate, and vinyl acetate. These comonomers (a3) can be used alone or in combination of two or more. Among them, methyl methacrylate and ethyl methacrylate are preferred from the viewpoint of improving cohesiveness when used as an adhesive.
[0096] When polymer (A) contains structural sites derived from comonomer (a3), its content relative to polymer (A) is typically 1% by mass or more, preferably 10% by mass or more, more preferably 15% by mass or more, and typically 70% by mass or less, preferably 60% by mass or less, more preferably 45% by mass or less, with a range of content such as 1 to 70% by mass. If the content of the comonomer (a3) is at or above the lower limit, there is a tendency for excellent adhesive strength of the adhesive layer; if it is at or below the upper limit, there is a tendency for excellent durability of the adhesive layer.
[0097] Furthermore, when methyl methacrylate and / or ethyl methacrylate are used as comonomers (a3), the content of structural portions derived from methyl methacrylate and / or ethyl methacrylate relative to polymer (A) is typically 1% by mass or more, preferably 2% by mass or more, more preferably 3% by mass or more, particularly preferably 4% by mass or more, and typically 40% by mass or less, preferably 30% by mass or less, more preferably 25% by mass or less, particularly preferably 10% by mass or less, with a range of content such as 1 to 40% by mass. If the content of structural portions derived from methyl methacrylate and / or ethyl methacrylate is at or above the aforementioned lower limit, there is a tendency for excellent adhesive strength of the adhesive layer; if it is below the upper limit, there is a tendency for excellent workability of polymer (A).
[0098] [An unsaturated monomer containing functional groups (a4)]
[0099] In the adhesive layer, a functionalized olefinic unsaturated monomer (a4) (excluding the hydroxyl-containing (meth)acrylate (a2)) may be used as a copolymer component of the polymer (A) as needed.
[0100] Examples of functionalized olefinic unsaturated monomers (a4) include monomers containing a nitrogen atom, carboxyl monomers, acetoacetyl monomers, isocyanate monomers, glycidyl monomers, etc.
[0101] Among them, considering the effects of imparting cohesion and promoting cross-linking, monomers containing functional groups with nitrogen atoms are preferred, further preferred are monomers containing amino groups or monomers containing amide groups, and particularly preferred are monomers containing amino groups.
[0102] Examples of amino-containing monomers include: methyl methacrylate, amino ethyl methacrylate, and other primary amino (meth)acrylates; tert-butylaminoethyl methacrylate, tert-butylaminopropyl methacrylate, and other secondary amino (meth)acrylates; ethylaminoethyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, dimethylaminopropyl methacrylate, diethylaminopropyl methacrylate, dimethylaminopropyl acrylamide, and other tert-amino (meth)acrylates.
[0103] Examples of amide-containing monomers include: (meth)acrylamide; N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, N-n-butyl (meth)acrylamide, diacetone (meth)acrylamide, N,N'-methylenebis(meth)acrylamide, and other N-alkyl (meth)acrylamides; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-ethylmethylacrylamide, N,N-diallyl (meth)acrylamide, and other N,N-dialkyl (meth)acrylamides; N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, and other hydroxyalkyl (meth)acrylamides; N-methoxymethyl (meth)acrylamide, N-(n-butoxymethyl)(meth)acrylamide, and other alkoxyalkyl (meth)acrylamides, etc.
[0104] Examples of carboxyl-containing monomers include: (meth)acrylic acid, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxypropyl phthalate, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxypropyl phthalate, 2-(meth)acryloyloxyethyl maleate, 2-(meth)acryloyloxypropyl maleate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxypropyl succinate, crotonic acid, fumaric acid, maleic acid, itaconic acid, etc.
[0105] Examples of acetoacetyl monomers include 2-(acetoacetoxy)ethyl methacrylate and allyl acetoacetate.
[0106] Examples of isocyanate-containing monomers include, for example, 2-(meth)acryloyloxyethyl isocyanate and their epoxide adducts.
[0107] Examples of the glycidyl-containing monomers include glycidyl (meth)acrylate and allyl (meth)acrylate.
[0108] These functionalized olefinic unsaturated monomers (a4) can be used alone or in combination with two or more.
[0109] When polymer (A) has a structural site derived from a functionalized olefinic unsaturated monomer (a4), its content relative to polymer (A) is typically 30% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably 5% by mass or less. If the content of the structural site derived from the functionalized olefinic unsaturated monomer (a4) is below the upper limit, polymer (A) tends to have excellent heat resistance.
[0110] [Other comonomers (a5)]
[0111] In the adhesive layer, other comonomers (a5) may be used as comonomers of the polymer (A) as needed.
[0112] Other comonomers (a5) mentioned above include, for example, methoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, butoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, butoxypolypropylene glycol (meth)acrylate, methoxypolytetramethylene glycol (meth)acrylate, butoxypolytetramethylene glycol (meth)acrylate, methoxypolyoxyethylene polyoxypropylene glycol (meth)acrylate, butoxypolyoxyethylene polyoxypropylene glycol (meth)acrylate, etc., which have an alkoxyalkylene glycol backbone, such as (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, and phenoxy (meth)acrylate. Aromatic (meth)acrylate monomers such as ethylene glycol (meth)acrylate, diethylene glycol (meth)acrylate, phenoxy polyethylene glycol (meth)acrylate, phenoxy polyethylene glycol-polypropylene glycol-(meth)acrylate, and nonylphenol ethylene oxide adduct (meth)acrylate; acrylonitrile, methacrylonitrile, styrene, α-methylstyrene, vinyl propionate, vinyl stearate, vinyl chloride, vinylidene chloride, alkyl vinyl ethers, vinyltoluene, vinylpyridine, vinylpyrrolidone, dialkyl itaconic acid, dialkyl fumarate, allyl alcohol, acryloyl chloride, methyl vinyl ketone, N-acrylamide methyltrimethylammonium chloride, allyltrimethylammonium chloride, and dimethylallyl vinyl ketone. These monomers can be used alone or in combination of two or more.
[0113] Furthermore, when the goal is to increase the molecular weight of polymer (A), other comonomers (a5) can be used in small quantities in combination with compounds having two or more olefinic unsaturated groups, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, and divinylbenzene. It should be noted that these compounds having two or more olefinic unsaturated groups are highly reactive and generally do not leave unreacted residues when used as polymerization components in acrylic copolymers.
[0114] When polymer (A) contains structural sites derived from other comonomers (a5), their content relative to polymer (A) is typically 50% by mass or less, preferably 40% by mass or less, and more preferably 20% by mass or less. If the content of the other comonomers (a5) is below the upper limit, there is a tendency to suppress the residue of unreacted comonomers (a5) and result in excellent heat resistance and adhesion of the adhesive layer.
[0115] The polymer (A) can be obtained by appropriately selecting the copolymer components and polymerizing them.
[0116] Methods for polymerizing the polymer (A) include conventionally known methods such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, and photopolymerization. Among these, solution polymerization is preferred from the perspective of being able to safely and stably manufacture the polymer (A) with any monomer composition.
[0117] Hereinafter, an example of a preferred method for manufacturing the polymer (A) is shown.
[0118] First, the copolymer components and polymerization initiator are mixed or added dropwise to an organic solvent to carry out solution polymerization, thereby obtaining a polymer (A) solution.
[0119] [Organic solvents]
[0120] Organic solvents used in polymerization reactions include, for example, aromatic hydrocarbons such as toluene and xylene, aliphatic hydrocarbons such as hexane, esters such as ethyl acetate and butyl acetate, aliphatic alcohols such as N-propanol and isopropanol, ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. These solvents can be used alone or in combination of two or more. Ethyl acetate is preferred among these solvents.
[0121] [Polymerization initiator]
[0122] As polymerization initiators used in the aforementioned polymerization reaction, azo-based polymerization initiators and peroxide-based polymerization initiators, which are commonly used free radical polymerization initiators, can be used. Examples of azo-based polymerization initiators include: 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobisisobutyronitrile, (1-phenylethyl)azodiphenylmethane, 2,2'-azobis(2,4-dimethylpentanonitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(4-methoxy-2,4-dimethylpentanonitrile), etc. Examples of peroxide-based polymerization initiators include: benzoyl peroxide, di-tert-butyl peroxide, cumene hydroperoxide, lauroyl peroxide, tert-butyl peroxypentanoate, tert-hexyl peroxypentanoate, tert-hexyl peroxydecanoate, diisopropyl percarbonate, diisobutyryl peroxide, etc. They can be used alone or in combination of two or more. Among them, 2,2'-azobis(2,4-dimethylpentanonitrile) is preferred.
[0123] The amount of the polymerization initiator used relative to 100 parts by mass of the copolymer component is typically 0.001 parts by mass or more, preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, further preferably 1 part by mass or more, particularly preferably 1.5 parts by mass or more, and most preferably 2 parts by mass or more. Furthermore, it is typically 10 parts by mass or less, preferably 8 parts by mass or less, more preferably 6 parts by mass or less, further preferably 4 parts by mass or less, particularly preferably 3 parts by mass or less, and most preferably 2.5 parts by mass or less. For example, the range of its usage is 0.001 to 10 parts by mass. If the amount of the polymerization initiator used is above the lower limit, there is a tendency for the polymerization rate of polymer (A) to increase while the residual monomer decreases, or for the weight-average molecular weight of polymer (A) to become within an appropriate range. If it is below the upper limit, there is a tendency to suppress unintended gelation of polymer (A).
[0124] [Aggregation conditions, etc.]
[0125] Regarding the polymerization conditions for solution polymerization, polymerization can be carried out according to previously known polymerization conditions. For example, the polymerization components and polymerization initiators can be mixed or added dropwise to the solvent, and polymerization can be carried out under specified polymerization conditions.
[0126] The polymerization temperature in the polymerization reaction is typically 40°C or higher, preferably 50°C or higher, more preferably 55°C or higher, and even more preferably 60°C or higher, and typically 120°C or lower, preferably 90°C or lower, more preferably 75°C or lower, and even more preferably 70°C or lower, for the sake of stable reaction. The range of this polymerization temperature is, for example, 40–120°C. If the polymerization temperature is above the lower limit, there is a tendency for the activity of the polymerization initiator to increase, the polymerization rate of polymer (A) to increase, and the residual monomer to decrease. If it is below the upper limit, there is a tendency to suppress unintended gelation of polymer (A).
[0127] Furthermore, the polymerization time in the polymerization reaction (the time until the start of the additional heat treatment, as described later) is not particularly limited, but is preferably 0.5 hours or more from the addition of the final polymerization initiator, particularly preferably 1 hour or more, further preferably 2 hours or more, and especially preferably 5 hours or more. The upper limit of the polymerization time is usually 72 hours, and the range of polymerization time is, for example, 0.5 to 72 hours.
[0128] It should be noted that, from the perspective of easy heat removal, it is preferable to carry out the polymerization reaction while the solvent is refluxed.
[0129] In the manufacture of the polymer (A), in order to reduce the amount of residual polymerization initiator, it is preferable to decompose the polymerization initiator by additional heat treatment.
[0130] The additional heat treatment is preferably performed at a temperature higher than the 10-hour half-life temperature of the polymerization initiator. Specifically, it is typically 40°C or higher, preferably 55°C or higher, and particularly preferably 75°C or higher, from the perspective of inhibiting gelation. Furthermore, it is typically 150°C or lower, preferably 130°C or lower, and particularly preferably 95°C or lower, from the perspective of inhibiting gelation. The temperature range is, for example, 40 to 150°C. If the temperature in the additional heat treatment is above the lower limit, there is a tendency for unreacted copolymer components and polymerization initiators to remain less in the polymer (A), and the time stability and thermal stability of the polymer (A) are improved. If it is below the upper limit, there is a tendency to inhibit the yellowing of the polymer (A).
[0131] In this way, polymer (A) can be obtained.
[0132] Furthermore, polymer (A) can also incorporate photoactive sites, such as polymeric carbon-carbon double bond groups, into its side chains. This improves the crosslinking efficiency of the resin composition, enabling crosslinking of the resin composition in a shorter time and increasing productivity.
[0133] As a method for introducing polymeric carbon-carbon double bond groups into the side chain of polymer (A), for example, the following method can be listed: a copolymer containing the above-mentioned hydroxyl (meth) acrylate (a2) and functional group olefinic unsaturated monomer (a4) is prepared, and then the compound having functional groups and polymeric carbon-carbon double bond groups capable of reacting with these functional groups is subjected to a condensation reaction or an addition reaction while maintaining the activity of the polymeric carbon-carbon double bond groups.
[0134] Examples of combinations of these functional groups include epoxy (glycidyl) and carboxyl, amino and carboxyl, amino and isocyanate, epoxy (glycidyl) and amino, hydroxyl and epoxy, and hydroxyl and isocyanate. Among these combinations, the combination of hydroxyl and isocyanate is preferred for ease of reaction control. Furthermore, a combination in which the copolymer has a hydroxyl group and the compound has an isocyanate group is preferred.
[0135] Examples of isocyanate compounds having polymerizable carbon-carbon double bond groups include the aforementioned 2-(meth)acryloyloxyethyl ester of isocyanate and their epoxide adducts.
[0136] From the viewpoint of improving adhesion and stress relaxation, the content of the compound having functional groups that can react with the aforementioned functional groups and polymerizable carbon-carbon double bond groups is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 1 part by mass or less, and particularly preferably 0.1 parts by mass or less, relative to 100 parts by mass of polymer (A). It should be noted that the lower limit is usually 0 parts by mass. Furthermore, the range of its content is, for example, 0 to 10 parts by mass.
[0137] In addition to being obtained by the method described above, the polymer (A) can also be obtained by preparing a slurry composition containing the copolymer or prepolymer, crosslinking agent (B), polymerization initiator (C), etc., and then irradiating the slurry composition with active energy rays to polymerize it.
[0138] From the perspective of suppressing the increase of shear storage modulus (G') at low temperatures, the glass transition temperature (Tg) of polymer (A) is preferably below -20°C, more preferably below -23°C, even more preferably below -25°C, particularly preferably below -30°C, and especially preferably below -40°C. It should be noted that, from the viewpoint of preventing glue leakage by maintaining the shear storage modulus at high temperatures at an appropriate value, the glass transition temperature (Tg) is typically above -70°C, preferably above -50°C. Furthermore, the range of glass transition temperature (Tg) is, for example, -70 to -20°C.
[0139] The glass transition temperature (Tg) is determined by reading the temperature at which the loss tangent (Tanδ) is maximized when dynamic viscoelasticity is measured using a dynamic viscoelasticity measuring device in shear mode at a frequency of 1 Hz.
[0140] For example, polymer (A) can be molded into a cylinder with a diameter of 8 mm (height of 0.8 mm) and the loss tangent (Tanδ) can be measured using a viscoelasticity measuring device (T.A. Instruments, "DHR 2") under the following measurement conditions.
[0141] (Measurement conditions)
[0142] • Measuring fixture: Φ8mm parallel plate.
[0143] • Strain: 0.1%.
[0144] • Frequency: 1Hz.
[0145] • Measurement temperature: -60~100℃.
[0146] • Heating rate: 5℃ / minute.
[0147] From the viewpoint of obtaining a resin composition with high cohesiveness, the weight-average molecular weight (Mw) of polymer (A) is preferably 400,000 or more, more preferably 500,000 or more, even more preferably 550,000 or more, and particularly preferably 600,000 or more.
[0148] Furthermore, considering workability and uniform mixing, the upper limit of the weight-average molecular weight (Mw) of polymer (A) is preferably 1.5 million or less, more preferably 1.2 million or less, even more preferably 1.1 million or less, and particularly preferably 1 million or less.
[0149] The range of the weight-average molecular weight (Mw) is, for example, 400,000 to 1,500,000.
[0150] In this invention, the weight-average molecular weight (Mw) can be determined, for example, as described below.
[0151] (Method for determining weight-average molecular weight)
[0152] 4 mg of polymer (A) can be dissolved in 12 mL of tetrahydrofuran (THF). The resulting substance is used as the test sample. The molecular weight distribution curve is determined using a gel permeation chromatography (GPC) analyzer (TOSOH HLC-8320GPC) under the following conditions, and the weight-average molecular weight (Mw) is calculated from this.
[0153] • Column protection: TSKguardcolumnHXL.
[0154] • Separation chromatographic column: TSKgelGMHXL (four columns).
[0155] Temperature: 40℃.
[0156] • Injection volume: 100μL.
[0157] • Polystyrene conversion.
[0158] Solvent: THF.
[0159] • Flow rate: 1.0 mL / min.
[0160] The content of the polymer (A) relative to the resin composition is typically 25% by mass or more, preferably 35% by mass or more, more preferably 45% by mass or more, particularly preferably 55% by mass or more, and furthermore, typically 99.9% by mass or less, preferably 99.5% by mass or less, more preferably 99% by mass or less, even more preferably 95% by mass or less, particularly preferably 90% by mass or less, and most preferably 85% by mass or less. Furthermore, its content ranges, for example, from 25% to 99.9% by mass.
[0161] [Cross-linking agent (B)]
[0162] The resin composition contains a crosslinking agent (B), which comprises a multifunctional crosslinking agent.
[0163] Therefore, the resin composition can efficiently form a cross-linked structure. If a cross-linked structure is formed in the adhesive layer using the resin composition, an adhesive layer with improved shape stability, improved storage and workability can be obtained. Furthermore, it can suppress the adhesive layer from overflowing from the ends during bonding. In addition, by forming a cross-linked structure in the adhesive layer, good adhesion and cohesion can be obtained.
[0164] In this adhesive layer, the crosslinking agent (B) comprises a crosslinking agent with three or more functional groups. Here, "crosslinking agent with three or more functional groups" means a molecule of a crosslinking agent containing three or more functional groups that have polymerization or crosslinking activity.
[0165] The crosslinking agent (B) preferably contains a crosslinking agent with 4 or more functions, more preferably a crosslinking agent with 5 or more functions. The crosslinking agent may also contain a crosslinking agent with 6 or more functions, for example, a crosslinking agent with 7 to 12 functions.
[0166] By including the crosslinking agent (B) with functional groups containing the lower limit or higher, an adhesive layer with good adhesion and / or cohesion after curing can be obtained. Furthermore, the crosslinking agent with 3 or more functional groups may also contain two or more different types of functional groups.
[0167] In one embodiment, the crosslinking agent (B) comprises at least 50% by mass of a trifunctional or higher crosslinking agent relative to the total crosslinking agent, preferably at least 60% by mass, more preferably at least 70% by mass, even more preferably at least 80% by mass, and particularly preferably at least 90% by mass. There is no particular upper limit, and it can also be 100% by mass. The range of the content of the trifunctional or higher crosslinking agent is, for example, 50 to 100% by mass.
[0168] Examples of crosslinking agents (B) include acrylic crosslinking agents, isocyanate crosslinking agents, epoxy crosslinking agents, aziridine crosslinking agents, melamine crosslinking agents, aldehyde crosslinking agents, amine crosslinking agents, and metal chelate crosslinking agents.
[0169] In one embodiment, the crosslinking agent (B) comprises an acrylic crosslinking agent. When the crosslinking agent (B) comprises an acrylic crosslinking agent, this is preferred from the perspective of easy control of the reaction. In this embodiment, it is more preferable that the crosslinking agent (B) comprises a polyfunctional (meth)acrylate.
[0170] Examples of the aforementioned polyfunctional (meth)acrylates include polyfunctional (meth)acrylate monomers and polyfunctional (meth)acrylate oligomers having two or more (meth)acryloyl groups. These can be used alone or in combination of two or more.
[0171] Examples of such multifunctional (meth)acrylate monomers include: pentanediol di(meth)acrylate, hexanediol di(meth)acrylate, heptadecyl di(meth)acrylate, octyldiol di(meth)acrylate, nonanediol di(meth)acrylate, decanedyl di(meth)acrylate, undecanediol di(meth)acrylate, dodecanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, glycerol di(meth)acrylate, neopentyl di(meth)acrylate, etc. Di(meth)acrylate of alcohol, di(meth)acrylate of glyceryl glycidyl ether, tricyclodecane dimethacrylate, tricyclodecanediethanol di(meth)acrylate, bisphenol A polyethoxydi(meth)acrylate, bisphenol A polypropoxydi(meth)acrylate, bisphenol F polyethoxydi(meth)acrylate, ethylene glycol di(meth)acrylate, trimethylolpropane trioxyethyl(meth)acrylate, ε-caprolactone modified tris(2-hydroxyethyl)isocyanurate tri(methyl)acrylate Acrylic esters, pentaerythritol tri(meth)acrylate, propoxylated pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate Tris(acryloyloxyethyl)isocyanurate, dipentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol penta(meth)acrylate, neopentyl glycol di(meth)acrylate of hydroxypentaerythritol, di(meth)acrylate of ε-caprolactone adduct of neopentyl glycol hydroxypentaerythritol, trimethylolpropane tri(meth)acrylate, trimethylolpropane polyethoxytri(meth)acrylate, di(trimethylolpropane)tetra(meth)acrylate, etc.
[0172] Examples of such multifunctional (meth)acrylate oligomers include: polyester (meth)acrylate oligomers, epoxy (meth)acrylate oligomers, urethane (meth)acrylate oligomers, polyether (meth)acrylate oligomers, and other multifunctional (meth)acrylate oligomers.
[0173] From the viewpoint of imparting a moderate degree of flexibility to the cured material, the crosslinking agent (B) preferably contains a diol structure or a urethane bond.
[0174] From the viewpoint of imparting cohesiveness, adhesive strength, shape stability, and / or durability when forming laminates, the content of the crosslinking agent (B) in the resin composition is typically 0.1 parts by mass or more, preferably 0.5 parts by mass or more, and more preferably 1 part by mass or more, relative to 100 parts by mass of the polymer (A). Furthermore, from the viewpoint of maintaining the flexibility of the adhesive layer, it is typically 10 parts by mass or less, preferably 8 parts by mass or less, more preferably 5 parts by mass or less, and extremely preferably 3 parts by mass or less. The range of the content of the crosslinking agent (B) is, for example, 0.1 to 10 parts by mass.
[0175] [Polymerization initiator (C)]
[0176] In this invention, the resin composition contains a polymerization initiator (C), which comprises a pyrolysis-type photopolymerization initiator.
[0177] In this specification, "polymerization initiator" refers to a general term for compounds that are activated by stimuli such as heat or light to generate anions, cations, free radicals, etc., that initiate polymerization reactions. In this invention, considering that the polymerization reactivity is less susceptible to the influence of polar groups or the surrounding environment, compounds that generate free radicals (free radical generators, free radical polymerization initiators) are preferably used.
[0178] In addition, "photopolymerization initiator" is a general term for polymerization initiators that are activated by irradiation with active energy rays such as electromagnetic waves and radiation.
[0179] In addition, "crack-type polymerization initiators" refer to polymerization initiators that break down intramolecular bonds upon activation.
[0180] Hereinafter, as an example of an embodiment, a detailed description will be given of the case where the polymerization initiator is a pyrolysis-type photopolymerization initiator that generates free radicals (pyrolysis-type photoradical polymerization initiator). However, as long as the effects of the present invention can be obtained, initiators other than free radical polymerization initiators may also be used.
[0181] Based on the free radical generation mechanism, free radical polymerization initiators can be broadly classified into two categories. More specifically, they can be divided into: cleavage-type free radical polymerization initiators, which generate free radicals by breaking down the single bonds of the initiator itself; and hydrogen abstraction-type free radical polymerization initiators, which generate free radicals by abstracting hydrogen from hydrogen donors in the system through the excited initiator.
[0182] The pyrolytic radical polymerization initiator is preferred in that it does not cause desaturation of the polymer and can suppress stiffening. Furthermore, when using a pyrolytic photoradical polymerization initiator, it is preferred in that it has high photosensitivity.
[0183] On the other hand, in any embodiment, the polymerization initiator (C) may also further comprise a hydrogen-abstracting radical polymerization initiator. A hydrogen-abstracting radical polymerization initiator is preferred in that it can introduce the polymer (A) into a cross-linked structure via a hydrogen-abstracting reaction, and is also preferred in that it does not produce photodecomposition products.
[0184] In this invention, from the viewpoint of suppressing stiffening caused by unintended desaturation of the polymer (A), the polymerization initiator (C) comprises a pyrolytic photopolymerization initiator. Preferably, 50% by mass or more of the polymerization initiator (C) is a pyrolytic photopolymerization initiator, more preferably 60% by mass or more, further preferably 70% by mass or more, particularly preferably 80% by mass or more, and in a specific embodiment, 100% by mass is composed of a pyrolytic photopolymerization initiator.
[0185] Examples of pyrolysis-type photopolymerization initiators include: 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxycyclohexylphenyl one, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propanoyl)benzyl]phenyl}-2-methyl-propane-1-one, oligomer (2-hydroxy-2-methyl-1-(4-(1-methylvinyl)phenyl)propane), 2-benzyl-2-dimethyl Benzylamino-1-(4-morpholinophenyl)butane-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholino)phenyl]-1-butanone, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, (2,4,6-trimethylbenzoyl)ethoxyphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)2,4,4-trimethylpentylphosphine oxide, and their derivatives, etc.
[0186] The content of polymerization initiator (C) in the resin composition is typically 0.1 parts by mass or more relative to 100 parts by mass of polymer (A), and on the other hand, it is 10 parts by mass or less, preferably 5 parts by mass or less, more preferably 4 parts by mass or less, particularly preferably 3 parts by mass or less, especially preferably 2.5 parts by mass or less, and most preferably 2 parts by mass or less. The range of the content of polymerization initiator (C) is, for example, 0.1 to 10 parts by mass.
[0187] By setting the content above the lower limit, there is a tendency to prevent poor curing; if it is below the upper limit, there is a tendency to easily suppress the decrease in solution stability, such as precipitation from the resin composition, and to easily suppress problems such as embrittlement and discoloration.
[0188] [Other ingredients]
[0189] Provided that the effects of the invention are not impaired, the resin composition may, as needed, contain, for example, various additives such as monofunctional (meth)acrylates, silane coupling agents, ultraviolet absorbers, plasticizers, tackifiers, antioxidants, light stabilizers, metal passivators, anti-aging agents, hygroscopic agents, rust inhibitors, and inorganic particles as "other components." Furthermore, reaction catalysts such as tertiary amine compounds, quaternary ammonium compounds, and tin lauryl compounds may be appropriately contained as needed. These may be used alone or in combination of two or more.
[0190] [Monofunctional (meth)acrylates]
[0191] The resin composition may also, if desired, contain a monofunctional (meth)acrylate having a (meth)acrylyl group. By containing a monofunctional (meth)acrylate having a (meth)acrylyl group, the molecular weight between the crosslinking points of the cured product can be increased, thus increasing the degree of freedom of movement of the molecular chains and making it easier to obtain a cured product with excellent stress relaxation properties, which is preferred from this perspective.
[0192] Examples of monofunctional (meth)acrylates include: ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isoamyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, dodecyl (meth)acrylate, isododecyl (meth)acrylate, tetradecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, benzyl (meth)acrylate, etc. Cyclopropyl methacrylate, cyclobutyl methacrylate, cyclopentyl methacrylate, cyclohexyl methacrylate, cycloheptyl methacrylate, cyclooctyl methacrylate, cyclononyl methacrylate, cyclodecyl methacrylate, isobornyl methacrylate, norbornyl methacrylate, adamantyl methacrylate, tricyclodecanediethanol acrylate, ethoxylated o-phenylphenol acrylate, 2-hydroxy-o-phenylphenol propyl acrylate, methoxy polyethylene glycol (meth)acrylate, methoxy polyethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, phenoxyethylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate Acrylic esters, phenoxy polyethylene glycol (meth)acrylates, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloyloxypropyl phthalate, 2-(meth)acryloyloxypropyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hexahydrophthalate, benzyl methacrylate, phenoxyethyl methacrylate, 2-naphthyl methacrylate, 9-anthracite methacrylate, 1-pyrene methyl methacrylate, tricyclodecanediethanol monoacrylate monocarboxylic acid, dicyclopentyl acrylate, 2-hydroxyethyl methacrylate, (methyl) 2-Hydroxypropyl acrylate, 3-Hydroxypropyl acrylate, 2-Hydroxybutyl acrylate, 4-Hydroxybutyl acrylate, Trimethylolpropane mono(meth)acrylate, Glyceryl mono(meth)acrylate, Pentaerythritol mono(meth)acrylate, Diglyceryl mono(meth)acrylate, Di(trimethylolpropane) mono(meth)acrylate, Dipentaerythritol mono(meth)acrylate, Ethoxylated Trimethylolpropane mono(meth)acrylate, Propoxylated Trimethylolpropane mono(meth)acrylate, Ethoxylated Glyceryl mono(meth)acrylate, Propoxylated Glyceryl mono(meth)acrylate, Ethoxylated Pentaerythritol mono(meth)acrylate, Propoxylated Pentaerythritol mono(meth)acrylate,Ethoxylated bis(trimethylolpropane) mono(meth)acrylate, propoxylated bis(trimethylolpropane) mono(meth)acrylate, epoxy-modified diglycerol mono(meth)acrylate, and epoxy-modified dipentaerythritol mono(meth)acrylate, etc., can also be listed as: monofunctional urethane (meth)acrylate, monofunctional epoxy (meth)acrylate, monofunctional polyester (meth)acrylate, and other monofunctional (meth)acrylate oligomers. These can be used individually or in combination of two or more.
[0193] Among them, monofunctional (meth)acrylic oligomers are preferred, including monofunctional urethane (meth)acrylates, monofunctional polyester (meth)acrylates, and monofunctional epoxy (meth)acrylates, with monofunctional urethane (meth)acrylates being more preferred.
[0194] The monofunctional urethane (meth)acrylate is highly polar and has a long chain length, thus achieving high resilience through polymer chain entanglement. In addition, it is particularly effective in achieving a low shear storage modulus through its oxypropylene structure with high molecular rotation.
[0195] In the case of containing monofunctional (meth)acrylate, from the viewpoint of imparting appropriate flexibility to the cured product by adjusting the crosslinking density, its content relative to 100 parts by mass of polymer (A) is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and particularly preferably 3 parts by mass or more. Regarding the upper limit, it is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, and particularly preferably 30 parts by mass or less, and the range of its content is, for example, 1 to 40 parts by mass.
[0196] [Silane coupling agent]
[0197] Silane coupling agents are organosilicon compounds containing one or more reactive functional groups and one or more alkoxy groups bonded to silicon atoms in their structure. Examples of such reactive functional groups include epoxy, (meth)acryloyl, mercapto, hydroxyl, carboxyl, amino, amide, and isocyanate groups. Among these, epoxy and mercapto groups are preferred from the perspective of durability balance.
[0198] From the perspective of durability and storage stability, alkoxy groups containing 1 to 8 carbon atoms are preferred as the alkoxy group bonded to the silicon atom, and methoxy or ethoxy groups are particularly preferred. It should be noted that the silane coupling agent may also have organic substituents other than the reactive functional group and the alkoxy group bonded to the silicon atom, such as alkyl or phenyl groups.
[0199] Examples of silane coupling agents include: 3-glycidyl etheroxypropyltrimethoxysilane, 3-glycidyl etheroxypropyltriethoxysilane, 3-glycidyl etheroxypropylmethyldiethoxysilane, 3-glycidyl etheroxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, etc., which are monomeric epoxy-containing silane coupling agents; partial hydrolysis and condensation of the silane compound; or the silane compound reacting with methyltriethoxysilane. Silane compounds formed by the co-condensation of alkyl silane compounds such as ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane are oligomeric epoxy-containing silane coupling agents; silane compounds such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, γ-mercaptopropyldimethoxymethylsilane, and 3-mercaptopropylmethyldimethoxysilane are monomeric mercapto-containing silane coupling agents; or a portion of the silane compound is hydrolyzed and condensed, or the silane compound is reacted with methyltriethoxysilane. Silane compounds formed by the co-condensation of alkyl silane compounds such as alkyl, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane are oligomer-type mercaptosilane coupling agents; 3-acryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropylmethyldiethoxysilane, 3-methacryloyloxypropyltriethoxysilane, etc., are (meth)acryloylsilane coupling agents; N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane... Methoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane and other aminosilane coupling agents; 3-isocyanate propyltriethoxysilane and other isocyanate silane coupling agents; vinyltrimethoxysilane, vinyltriethoxysilane and other vinylsilane coupling agents, etc.
[0200] They can be used individually or in combination of two or more.
[0201] Among them, considering superior durability, epoxy-containing silane coupling agents and mercapto-containing silane coupling agents are preferred, with epoxy-containing silane coupling agents being particularly preferred.
[0202] When the resin composition contains a silane coupling agent, its content relative to 100 parts by weight of polymer (A) is typically 0.005 parts by weight or more, preferably 0.01 parts by weight or more, particularly preferably 0.05 parts by weight or more, and typically 10 parts by weight or less, preferably 5.0 parts by weight or less, particularly preferably 1.0 parts by weight or less, with a range of content such as 0.05 to 10 parts by weight. If its content is within the range described above, there is a tendency for improved adhesion and durability.
[0203] [Ultraviolet absorber]
[0204] Examples of UV absorbers include benzophenone-based, benzotriazole-based, triazine-based, salicylic acid-based, cyanoacrylate-based, and benzoxazine-based UV absorbers. These UV absorbers can be used alone or in combination of two or more.
[0205] The content of the ultraviolet absorber, relative to 100 parts by weight of polymer (A), is typically 0.01 parts by weight or more, preferably 0.1 parts by weight or more, more preferably 0.5 parts by weight or more, and is typically 20 parts by weight or less, preferably 15 parts by weight or less, more preferably 10 parts by weight or less. The range of its content is 0.01 to 20 parts by weight, etc. If the content is above the lower limit, there is a tendency for improved lightfastness reliability; if it is below the upper limit, there is a tendency for improved resistance to yellowing.
[0206] [Plasticizer]
[0207] The plasticizer is not limited, but examples include at least one selected from the group consisting of polyisobutylene, polyisoprene, polybutadiene, amorphous polyolefins and their copolymers, silicone, polyacrylate, oligomeric polyurethane, ethylene-propylene copolymers, etc., and any combination or mixture thereof. Among them, polyisobutylene is preferred.
[0208] Examples of polyisobutylene plasticizers include substances commercially available from BASF under the trade name OPPANOL, particularly those selected from the OPPANOL B series.
[0209] When the resin composition contains a plasticizer, its content is not particularly limited, but is usually 0.1 parts by mass or more, preferably 0.5 parts by mass or more, relative to 100 parts by mass of polymer (A), and is usually 20 parts by mass or less, preferably 15 parts by mass or less, and its content range is, for example, 0.1 to 20 parts by mass.
[0210] [Tackifier]
[0211] To improve the adhesion of the adhesive layer, the resin composition may contain a tackifier.
[0212] Examples of tackifiers include: terpene resins such as polyterpene resins (e.g., α-pinene resins, β-pinene resins, and limonene resins) and aromatic modified polyterpene resins (e.g., phenol-modified polyterpene resins), coumarone-indene resins, petroleum-based resins such as C5 hydrocarbon resins, C9 hydrocarbon resins, C5 / C9 hydrocarbon resins, and dicyclopentadiene resins, modified rosin, hydrogenated rosin, polymerized rosin, and rosin esters.
[0213] When the resin composition contains a tackifier, its content is not particularly limited, but is usually 0.1 parts by mass or more, preferably 0.5 parts by mass or more, relative to 100 parts by mass of polymer (A), and is usually 20 parts by mass or less, preferably 15 parts by mass or less, and its content range is, for example, 0.1 to 20 parts by mass.
[0214] [Rust Inhibitor]
[0215] To prevent corrosion in cases where the adhered material contains corrosive parts such as metal wiring, the resin composition may contain a rust inhibitor.
[0216] Examples of rust inhibitors include triazoles and benzotriazoles.
[0217] When the resin composition contains a rust inhibitor, its content relative to 100 parts by mass of polymer (A) is typically 0.01 parts by mass or more, preferably 0.1 parts by mass or more, and furthermore, 5 parts by mass or less, preferably 3 parts by mass or less, and its content range is, for example, 0.01 to 5 parts by mass.
[0218] <<Manufacturing Method of This Adhesive Layer>>
[0219] Next, the manufacturing method of this adhesive layer will be described.
[0220] However, the following description is an example of a method for manufacturing this adhesive layer, and this adhesive layer is not limited to adhesive layers manufactured by this method.
[0221] This adhesive layer can be manufactured by preparing a resin composition containing the polymer (A), crosslinking agent (B), polymerization initiator (C), and other components as needed, molding the resin composition into a layer, allowing it to undergo a crosslinking, i.e., polymerization reaction and cure it, and performing appropriate processing as needed.
[0222] The resin composition can be prepared simply by mixing the raw materials using a temperature-adjustable mixer (e.g., a single-screw extruder, a twin-screw extruder, a planetary mixer, a twin-screw mixer, a pressure kneader, etc.).
[0223] It should be noted that when mixing various raw materials, various additives such as silane coupling agents and antioxidants can be pre-mixed with the resin and then supplied to the mixer, or all materials can be pre-melted and mixed before being supplied, or a masterbatch can be made by pre-concentrating the additives in the resin and then supplied.
[0224] Known methods can be used to form the resin composition into a layer, such as wet lamination, dry lamination, extrusion casting using a T-die, extrusion lamination, calendering, blown film molding, injection molding, and liquid injection curing. Among these, wet lamination, extrusion casting, and extrusion lamination are preferred when manufacturing this adhesive layer.
[0225] Furthermore, the resin composition can be cured by irradiation with active energy rays or by heating. When using active energy rays, the adhesive layer can be manufactured by irradiating a molded body of the resin composition, such as a layered molded body, with active energy rays. It should be noted that, in addition to irradiation with active energy rays, heating can also be used to further achieve curing.
[0226] Furthermore, there are no particular limitations on the irradiation energy, irradiation time, irradiation method, etc. of the active energy rays, as long as they can activate the polymerization initiator (C) and polymerize photoreactive components such as (meth)acrylate compounds.
[0227] Examples of active energy rays used in the irradiation include far-ultraviolet rays, ultraviolet rays, near-ultraviolet rays, infrared rays, visible light, X-rays, alpha rays, beta rays, gamma rays, electron beams, proton beams, neutron beams, and other ionizing radiation. Ultraviolet rays are preferred from the viewpoint of suppressing damage to the components of the optical device and controlling the reaction. Furthermore, ultraviolet rays are also preferred from the perspectives of curing speed, ease of obtaining the irradiation device, and cost.
[0228] Examples of light sources for ultraviolet irradiation include high-pressure mercury lamps, ultra-high-pressure mercury lamps, low-pressure mercury lamps, carbon arc lamps, metal halide lamps, xenon lamps, chemical lamps, electrodeless discharge lamps, and LED (Light Emitting Diode) lamps, which emit light in the 150–450 nm wavelength range. Among these, high-pressure mercury lamps, metal halide lamps, and LED lamps are preferred.
[0229] From a curing perspective, the preferred irradiation dose (cumulative light intensity) is 0.03 J / cm². 2 The above, more preferably 0.1 J / cm 2 The above is further preferably 0.3 J / cm. 2 In addition to the above, 3J / cm is preferred. 2The following is more preferably 2J / cm 2 The following is a further preferred value of 1.5 J / cm. 2 the following.
[0230] Furthermore, this adhesive layer can also be provided in the form of an adhesive layer with a release film, having a structure in which a release film is laminated on one or both sides. From the viewpoint of preventing adhesion and foreign matter attachment, it is preferable that both sides of this adhesive layer are covered with a release film.
[0231] When release films are provided on both sides of the adhesive layer, it is preferable to form a laminate consisting of a light release film with relatively low peel strength and a heavy release film with relatively high peel strength.
[0232] In the case of an adhesive layer with release films on both sides, when in use, one release film (light peel film) is first peeled off to expose one side of the adhesive layer, and then it is bonded to the component of the image display device (designated as the first component). The other side of the adhesive layer exposed by peeling off the other release film (heavy peel film) is then bonded to the other side of the adhesive layer, which is exposed by peeling off the other release film (designated as the second component).
[0233] As the release film, a known release film can be appropriately used.
[0234] As the substrate for the release film, for example, a substrate or release paper that has been treated by coating a release agent such as silicone resin onto a polyester film, polyolefin film, polycarbonate film, polystyrene film, acrylic film, triacetyl cellulose film, fluoropolymer film, etc., and has undergone release treatment can be appropriately selected.
[0235] Among them, polyester film is preferred, and polyethylene terephthalate (PET) film is more preferred. Considering its superior properties such as transparency, mechanical strength, heat resistance, and flexibility, biaxially stretched PET film is particularly preferred.
[0236] Furthermore, a release film can be used on the substrate having a release layer formed by curing a silicone-based release agent with silicone resin as the main component.
[0237] The peel force between the adhesive layer and the release film is preferably 0.05 N / cm or more, more preferably 0.06 N / cm or more, even more preferably 0.07 N / cm or more, and preferably 1.5 N / cm or less, more preferably 1.2 N / cm or less, even more preferably 1.0 N / cm or less. The peel force between the adhesive layer and the release film is a measured value obtained through a 180° peel test at a test speed of 300 mm / min. If the peel force between the adhesive layer and the release film is within the specified range, peel marks when peeling the release film from the adhesive layer can be prevented.
[0238] Typically, when a highly flexible adhesive layer is made into an adhesive layer with a release film, if the release film has a high peel force, the adhesive layer is soft. Therefore, there is a tendency for the adhesive layer to deform when the release film is peeled off, which can easily produce peel marks.
[0239] Therefore, the release film used in the highly flexible adhesive layer, especially the light-release film, is preferably a release film that can be peeled off with less force compared to the light-release type release films that are commonly used in the past.
[0240] However, if the release agent layer is thickened to facilitate easy peeling of the release film, depending on the type of release agent used, components from the release agent layer may sometimes transfer to the surface of the adhesive layer, compromising the reliability of the adhesive layer. Therefore, a release film with good release properties from the adhesive layer and minimal transfer of the release agent to the adhesive layer is preferred.
[0241] The peak intensity of silicon atoms on the adhesive surface exposed after peeling off the release film from this adhesive layer, as measured using a fluorescence X-ray analysis device, is preferably 100 cps or less. If the peak intensity is 100 cps or less, the reliability of forming a laminate from the adhesive layer will not be compromised by the release agent transferred to the adhesive layer surface, which is therefore preferable. From this viewpoint, the peak intensity is more preferably 90 cps or less, further preferably 80 cps or less, and particularly preferably 70 cps or less. It should be noted that the lower limit is typically 0 cps.
[0242] The thickness of the release film is not particularly limited. However, from the viewpoint of processability and workability, it is preferably 10 μm or more, more preferably 25 μm or more, particularly preferably 35 μm or more, and preferably 250 μm or less, more preferably 200 μm or less, and particularly preferably 190 μm or less.
[0243] The release film can be embossed, processed with various concave and convex shapes (conical, pyramidal, or hemispherical shapes, etc.) as needed, and can also undergo various surface treatments such as corona treatment, plasma treatment, and primer treatment.
[0244] In addition, as another embodiment of the method for manufacturing this adhesive layer, the resin composition can be dissolved in a suitable solvent and various coating methods can be used.
[0245] In the case of using a coating method, in addition to the curing based on active energy ray irradiation described above, the adhesive layer can also be obtained by curing with heat. Furthermore, in the case of using a coating method, the thickness of the adhesive layer can be adjusted by the coating thickness and the concentration of solid components in the coating liquid.
[0246] The coating method can be, for example, conventional methods such as roller coating, die coating, gravure coating, comma coating, screen printing, and bar coating.
[0247] When manufacturing this adhesive layer using the coating method described above, for example, the resin composition can be dissolved in a solvent, coated onto the release film, the component sheet, or the component of the flexible image display device, and dried. It can then be cured by irradiation with the aforementioned active energy rays, thereby forming this adhesive layer.
[0248] Furthermore, the adhesive layer obtained by the coating method can also be laminated with the aforementioned release film as needed. In this case, the adhesive layer can be formed by coating and drying the release film, curing it by irradiation with active energy rays, and then laminating the release film on top. Alternatively, the adhesive layer can be formed by coating and drying the release film, laminating the release film, and then curing it by irradiation with active energy rays.
[0249] The solvent can be any solvent that dissolves the resin composition; there are no particular limitations. Examples include ester solvents such as methyl acetate, ethyl acetate, butyl acetate, methyl acetoacetate, and ethyl acetoacetate; ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; aromatic solvents such as toluene and xylene; and alcohol solvents such as methanol, ethanol, and propanol. These solvents can be used alone or in combination of two or more. Considering factors such as solubility, drying properties, and price, ethyl acetate, acetone, methyl ethyl ketone, and toluene are preferred, with ethyl acetate being particularly preferred.
[0250] Regarding the solvent content, from the perspective of drying properties, it is preferably 600 parts by mass or less, more preferably 500 parts by mass or less, even more preferably 400 parts by mass or less, and particularly preferably 300 parts by mass or less, relative to 100 parts by mass of polymer (A). On the other hand, it is preferably 1 part by mass or more, more preferably 50 parts by mass or more, even more preferably 100 parts by mass or more, and particularly preferably 150 parts by mass or more.
[0251] The solvent content in the dried resin composition is preferably 1% by mass or less, more preferably 0.5% by mass or less, particularly preferably 0.1% by mass or less, and most preferably 0% by mass.
[0252] The drying temperature is typically 40°C or higher, preferably 45°C or higher, more preferably 50°C or higher, and particularly preferably 55°C or higher. Furthermore, it is typically 150°C or lower, preferably 140°C or lower, more preferably 130°C or lower, and particularly preferably 120°C or lower. For example, the temperature range is 40 to 150°C. Within this temperature range, thermal deformation of the release film can be suppressed, and the solvent can be removed effectively and relatively safely.
[0253] The drying time is typically 1 minute or more, preferably 3 minutes or more, and also typically 30 minutes or less, preferably 25 minutes or less, and more preferably 20 minutes or less. For example, a time range of 1 to 30 minutes is acceptable. Within this time range, the solvent can be effectively and sufficiently removed.
[0254] Examples of drying methods include drying using a dryer, drying with heated rollers, and drying by blowing hot air onto the film. Among these, a dryer is preferred from the viewpoint of being able to perform drying uniformly and easily. These methods can be used individually or in combination of two or more.
[0255] From the viewpoint of preventing adhesion and foreign matter attachment, the adhesive layer obtained by the coating method can also have the release film provided on at least one side.
[0256] That is, the adhesive layer obtained by the coating method can also be provided in the form of an adhesive layer with a release film (adhesive layer laminate) having a structure in which a release film is laminated on one or both sides.
[0257] Furthermore, when the resin composition is a slurry composition containing a prepolymer formed by copolymerization of copolymer components and / or partially copolymerized copolymer components, a crosslinking agent (B), a polymerization initiator (C), etc., this adhesive layer can be obtained by the following manufacturing method (slurry method).
[0258] In the slurry method, a slurry composition is prepared and polymerized by irradiating the slurry composition with active energy rays. Then, the slurry composition, with the addition of crosslinking agent (B), polymerization initiator (C), etc., as needed, is coated onto a release film or the like using the coating method, and then irradiated with active energy rays and heated to cure it, thereby obtaining the adhesive layer.
[0259] The crosslinking agent (B), polymerization initiator (C), etc., can be added to the slurry composition from the beginning, or they can be added to the slurry composition after prepolymerization. Moreover, in the slurry method, polymerization and curing can be carried out in one step.
[0260] In addition, as another embodiment of the slurry method, the slurry composition can be dissolved in a solvent, coated onto a release film and dried, and then polymerized and cured by irradiation with active energy rays, thereby producing the adhesive layer.
[0261] In the slurry method, the release film, active energy rays, solvent, resin composition preparation method, coating method, active energy ray irradiation conditions, drying conditions, etc., can all be prepared in accordance with the foregoing description.
[0262] From the viewpoint of preventing adhesion and foreign matter attachment, the adhesive layer obtained by the slurry method can also have the release film provided on at least one side.
[0263] That is, the adhesive layer obtained by the slurry method can also be provided in the form of an adhesive layer with a release film (adhesive layer laminate) having a structure in which a release film is laminated on one or both sides.
[0264] The adhesive layer thus obtained can be a single layer consisting only of the adhesive layer formed by the resin composition, or it can be a multilayer consisting of multiple layers of the adhesive layer and other adhesive layers.
[0265] <<Viscoelastic properties of this adhesive layer>>
[0266] <Shear storage modulus (G')>
[0267] The shear storage modulus (G') that the adhesive layer can possess will be described in detail below. In this specification, the shear storage modulus at a specific temperature (X°C) is referred to as the shear storage modulus (G'(X°C)). The shear storage modulus (G'(X°C)) is measured, for example, as described below.
[0268] After repeatedly stacking the adhesive layer to adjust the thickness to 0.7–1.2 mm (e.g., 0.8 mm), the sample is punched to a diameter of 8 mm. The resulting sample is then subjected to dynamic viscoelasticity measurements using a rheometer under the following conditions: 8 mm diameter parallel plate fixture, frequency: 1 Hz, measurement temperature: -50–150 °C, heating rate: 5 °C / min. The shear storage modulus (G') value at each temperature is recorded.
[0269] In one embodiment of the present invention, the shear storage modulus (G'(-30°C)) of the adhesive layer at -30°C is typically 100 kPa or more, preferably 150 kPa or more, more preferably 200 kPa or more, even more preferably 250 kPa or more, typically 1200 kPa or less, preferably 1000 kPa or less, more preferably 700 kPa or less, even more preferably 600 kPa or less.
[0270] By setting the shear storage modulus (G'(-30°C)) of the adhesive layer at -30°C to above the lower limit, an adhesive layer with moderate cohesion and shape stability can be obtained. By setting the shear storage modulus (G'(-30°C)) of the adhesive layer at -30°C to below the upper limit, for example, when the adhesive layer is attached to a component sheet to form a laminate, especially at low to high temperatures, the interlayer stress during bending of the laminate can be reduced, and the peeling and damage of the component sheet or the flexible image display device component caused by stress can be suppressed.
[0271] In one embodiment of the present invention, the shear storage modulus (G'(-20°C)) of the adhesive layer at -20°C is 300 kPa or less, preferably 250 kPa or less, more preferably 200 kPa or less, even more preferably 180 kPa or less, typically 10 kPa or more, preferably 30 kPa or more, more preferably 50 kPa or more, even more preferably 100 kPa or more, and particularly preferably 120 kPa or more.
[0272] By setting the shear storage modulus (G'(-20°C)) of the adhesive layer below the upper limit, flexibility can be maintained even at low temperatures, resulting in an adhesive layer with good bending adaptability at low temperatures. Furthermore, by setting the shear storage modulus (G'(-20°C)) of the adhesive layer above the lower limit, moderate cohesion can be obtained at low temperatures.
[0273] In one embodiment of the present invention, the shear storage modulus (G'(25°C)) of the adhesive layer at 25°C is generally 5 kPa or more, preferably 10 kPa or more, more preferably 15 kPa or more, further preferably 20 kPa or more, particularly preferably 30 kPa or more, generally 100 kPa or less, preferably 80 kPa or less, and more preferably 50 kPa or less.
[0274] By making the shear storage modulus (G'(25°C)) of the adhesive layer at 25°C above the lower limit, an adhesive layer with good shape stability can be obtained; by making the shear storage modulus (G'(25°C)) of the adhesive layer at 25°C below the upper limit, an adhesive layer with high adhesion can be obtained.
[0275] In one embodiment of the present invention, the shear storage modulus (G'(60°C)) of the adhesive layer at 60°C is typically 5 kPa or more, preferably 10 kPa or more, more preferably 15 kPa or more, further preferably 20 kPa or more, typically 40 kPa or less, preferably 35 kPa or less, and more preferably 30 kPa or less.
[0276] By making the shear storage modulus (G'(60°C)) of the adhesive layer at 60°C above the lower limit, an adhesive layer with good shape stability can be obtained; by making the shear storage modulus (G'(60°C)) of the adhesive layer at 60°C below the upper limit, an adhesive layer with high adhesion can be obtained.
[0277] In one embodiment of the present invention, the shear storage modulus (G'(85°C)) of the adhesive layer at 85°C is 5.0 kPa or more, more preferably 8 kPa or more, even more preferably 10 kPa or more, particularly preferably 12 kPa or more, and is 30 kPa or less, preferably 28 kPa or less, more preferably 27 kPa or less, and even more preferably 26 kPa or less.
[0278] By setting the shear storage modulus (G'(85°C)) of the adhesive layer at 85°C above the lower limit, an adhesive layer with sufficient curing degree and shape stability at high temperature can be obtained. By setting the shear storage modulus (G'(85°C)) of the adhesive layer at 85°C below the upper limit, an adhesive layer with moderate flexibility and not too high curing degree can be obtained.
[0279] As a method for adjusting the shear storage modulus (G') at various temperatures to the aforementioned range, examples include adjusting the composition, molecular weight, crosslinking agent (B), and type and content of polymerization initiator (C) of polymer (A). In addition, examples include adjusting the amount of active energy radiation. However, this method is not limited to these methods.
[0280] Glass transition temperature
[0281] In one embodiment, the glass transition temperature (Tg) of the adhesive layer of the present invention, defined by the maximum value of Tanδ obtained by dynamic viscoelasticity measurement in a shear mode at a frequency of 1 Hz, is preferably -15°C or lower, more preferably -20°C or lower, even more preferably -25°C or lower, particularly preferably -30°C or lower, and generally -100°C or higher, preferably -90°C or higher, more preferably -80°C or higher, and even more preferably -70°C or higher. The range of glass transition temperature is, for example, -100 to -15°C. By setting the glass transition temperature below the upper limit, there is a tendency to obtain an adhesive layer that exhibits good flexural adaptability even at low temperatures. Furthermore, by setting the glass transition temperature above the lower limit, there is a tendency to obtain moderate cohesion.
[0282] The glass transition temperature (Tg) is obtained by reading the temperature at which the loss tangent (Tanδ) reaches its maximum value, i.e., the peak temperature, from the dynamic viscoelastic spectral data in the shear mode obtained using the same method as the shear storage modulus (G') described above.
[0283] It should be noted that, in the viscoelastic spectrum, the "peak temperature" in the case of multiple maxima refers to the temperature at which the maximum value is reached.
[0284] As a method for adjusting the glass transition temperature (Tg) to the range, examples include adjusting the composition, molecular weight, crosslinking agent (B), and type and content of polymerization initiator (C) of polymer (A). In addition, examples include adjusting the amount of active energy radiation. However, the method is not limited to these methods.
[0285] From the viewpoint of obtaining adequate cohesion, the gel fraction of the adhesive layer is 45% or more, preferably 50% or more, more preferably 55% or more, and even more preferably 60% or more. Furthermore, from the viewpoint of obtaining adequate softness, it is 95% or less, preferably 90% or less, more preferably 85% or less, even more preferably 80% or less, and particularly preferably 75% or less. The range of gel fraction is, for example, 45% to 95%.
[0286] The gel fraction is determined, for example, as described below.
[0287] Prepare a pre-measured mass of the adhesive layer and a 150-mesh SUS (stainless steel) metal mesh. Next, wrap the adhesive layer with the SUS metal mesh and impregnate it in ethyl acetate at 23°C for 24 hours. Then, dry it at 70°C for 4.5 hours, and measure the mass of the adhesive layer along with the SUS metal mesh. Subtract the mass of the SUS metal mesh from this mass to determine the mass of the undissolved adhesive layer remaining in the metal mesh (mass after impregnation). Then, calculate the gel fraction (%) as the percentage of the mass of the undissolved adhesive layer remaining in the metal mesh (mass after impregnation) relative to the mass of the adhesive layer before ethyl acetate impregnation (mass before impregnation).
[0288] As a method for adjusting the gel fraction to the range, examples include adjusting the composition, molecular weight, crosslinking agent (B), and type and content of polymerization initiator (C) of polymer (A). In addition, examples include adjusting the amount of active energy radiation. However, these methods are not the only options.
[0289] <Adhesion>
[0290] In one embodiment, the adhesive layer has an adhesion force of 5.0 N / cm or more relative to a plasma-treated polyethylene terephthalate (PET) substrate at a temperature of 23°C and a peeling speed of 300 mm / min.
[0291] By ensuring an adhesive force of 5.0 N / cm or more relative to the PET substrate, peeling of the adhesive layer end faces is prevented, resulting in excellent bonding reliability at the peripheral ends. From this perspective, an adhesive force of 6.0 N / cm or more relative to the PET substrate is more preferably preferred, further preferably 6.5 N / cm or more, and particularly preferably 8.0 N / cm or more. It should be noted that the upper limit of the adhesive force is not particularly limited; from the viewpoint of reprocessability, it is typically 50 N / cm, preferably 30 N / cm, and the range of this adhesive force is, for example, 5.0 to 50 N / cm.
[0292] In one embodiment, the adhesive layer preferably has an adhesion force of 4.5 N / cm or more relative to the plasma-treated glass substrate at a temperature of 23°C and a peeling speed of 300 mm / min.
[0293] By achieving an adhesive force of 4.5 N / cm or more relative to the glass substrate, there is a tendency to obtain excellent bonding reliability at the peripheral ends without peeling off the end face of the adhesive layer. From this viewpoint, an adhesive force of 5.0 N / cm or more relative to the glass substrate is more preferably preferred, and even more preferably 6.0 N / cm or more. It should be noted that there is no particular upper limit to the adhesive force; from the viewpoint of reprocessability, it is typically 50 N / cm, preferably 30 N / cm, and the range of adhesive forces is, for example, 4.5 to 50 N / cm.
[0294] The adhesive strength is measured, for example, as described below.
[0295] A 100 μm thick polyethylene terephthalate (PET) film is laminated to this adhesive layer, and another roller is pressed onto a plasma-treated polyethylene terephthalate (PET) or soda-lime glass substrate to form a laminated product. The laminated product is then subjected to autoclave treatment (60°C, 0.2 MPa gauge pressure, 20 minutes) and final bonding is performed. The resulting product is used as a sample for adhesive strength testing. Using this sample, peeling is performed at 23°C and 50% RH, with a peel angle of 180° and a peel speed of 300 mm / min. The peel force (N / cm) at this point is taken as the adhesive force.
[0296] <Recovery Rate>
[0297] Regarding this adhesive layer, the maximum strain (γ) after applying a pressure of 10 kPa for 600 seconds with a thickness of 0.5–1.2 mm at 25°C is measured. max(25) ) and then the strain (γ) after stress is unloaded and after 600 seconds min(25)The recovery rate calculated using the following formula is preferably 70% or higher, more preferably 75% or higher. It should be noted that a higher recovery rate is preferred, therefore the upper limit of the recovery rate is 100%, and the range of the recovery rate is, for example, 70-100%.
[0298] Recovery rate (%) = [(γ)] max(25) -γ min(25) ) / γ max(25) ]×100
[0299] Furthermore, the maximum strain (γ) max(25) The content is preferably 600% or less, more preferably 550% or less, even more preferably 500% or less, particularly preferably 400% or less, and particularly preferably 350% or less.
[0300] Furthermore, in a specific embodiment, the thickness in the recovery rate test is 0.6 mm or more and 1.00 mm or less, and can be set to 0.8 mm.
[0301] If this adhesive layer has such a recovery rate, it can be made into an adhesive layer with excellent flexibility. Even if this adhesive layer is pasted onto a component piece and folded at low or high temperatures, the adhesive layer will not leave creases caused by being placed in a bent state.
[0302] <Room Temperature Dynamic Bending Test>
[0303] Preferably, no creases were observed in the adhesive layer after a dynamic bending test at room temperature, and no peeling was observed at the interface with the adherend. There are no particular limitations on the conditions for the dynamic bending test at room temperature, and conventional methods can be used. The evaluation values in this specification can be determined using the methods described in the examples below.
[0304] <Static Bending Test under High Temperature and High Humidity>
[0305] This adhesive layer preferably exhibits no peeling observed at the interface with the adherend after a static bending test under high temperature and high humidity, and demonstrates high resilience (e.g., an inward angle of 30° or more at the bend). The conditions for the static bending test under high temperature and high humidity are not particularly limited, and conventional methods can be used. The evaluation values in this specification can be determined using the methods described in the examples below.
[0306] <Preferred uses of this adhesive layer>
[0307] In one embodiment, this adhesive layer is suitable for bonding optical components. Specifically, it is suitable for bonding components constituting a display, especially components used in manufacturing a display, and is suitable as an adhesive layer for bonding an image display panel to a protective panel, touch panel, or other image display device component disposed on its front side (visual confirmation side), or to a component constituting the image display device.
[0308] It should be noted that the same components as those described later can be used for the components constituting the image display device.
[0309] <<Layered Structures>>
[0310] In one embodiment, the present invention is a laminate comprising one or more components for an image display device and the adhesive layer. (Hereinafter, the laminate of this embodiment is sometimes referred to as "this laminate")
[0311] Furthermore, in one embodiment, the laminate is a laminate comprising two image display device constituent components and an adhesive layer sandwiched between the two image display device constituent components.
[0312] The adhesive layer in the constituent elements of this laminate can retain the structure and features of the aforementioned adhesive layer. The elements other than this adhesive layer will be described below.
[0313] (Components of an image display device)
[0314] As constituent components of the image display device constituting this laminate, examples include flexible image display device constituent components. Examples of such flexible image display device constituent components include: image display panels such as organic electroluminescent (EL) displays, cover lenses (cover films), surface protection panels (surface protection films), polarizers, color filters, polarizing elements, phase difference films, barrier films, viewing angle compensation films, brightness enhancement films, contrast enhancement films, diffusion films, semi-transmissive reflective films, electrode films, transparent conductive films, metal mesh films, touch sensor films, etc. Any one of these components, or a combination of two or more, can be used. Examples include combinations of flexible displays with other flexible image display device constituent components, and combinations of cover lenses with other flexible image display device constituent components.
[0315] Preferably, one of the two image display device components is a surface protection panel, and the other is a component consisting of any one or any combination of two or more of the following: a touch sensor film, an image display panel, a color filter, a polarizing element, and a phase difference film.
[0316] It should be noted that the components of a flexible image display device refer to bendable components, especially components that can be repeatedly bent. In particular, components that can be fixed into a bent shape with a radius of curvature of 25 mm or more are preferred, especially components that can withstand repeated bending with a radius of curvature of less than 25 mm, and more preferably components with a radius of curvature of less than 3 mm.
[0317] In the above configuration, the main components that make up the flexible image display device include resin sheets or glass.
[0318] Examples of materials that can be used for this resin sheet include polyester resin, cyclic olefin resin, triacetyl cellulose resin, polymethyl methacrylate resin, polyurethane, epoxy resin, polyimide resin, and aramid resin. These can be one type of resin or two or more types of resin. Preferably, the resin sheet contains at least one resin selected from the group consisting of polyester resin, cyclic olefin resin, triacetyl cellulose resin, polymethyl methacrylate resin, epoxy resin, polyimide resin, aramid resin, and polyurethane resin as its main component.
[0319] Here, "main component" refers to the component that accounts for the largest weight percentage among the components constituting the flexible image display device components. Specifically, it is preferably 50% or more by mass of the resin composition (resin sheet) forming the flexible image display device components, more preferably 55% or more by mass, and particularly preferably 60% or more by mass.
[0320] Furthermore, the components of flexible image display devices can also be formed from thin-film glass.
[0321] In the above configuration, the tensile strength of either of the two flexible image display device components, namely the first flexible image display device component, at 25°C as measured according to ASTM D882, is preferably 10 MPa or more, more preferably 15 MPa or more, particularly preferably 20 MPa or more, and further preferably 900 MPa or less, more preferably 800 MPa or less, and particularly preferably 700 MPa or less.
[0322] If the tensile strength (ASTM D882) at 25°C of a component of a flexible image display device is within the range described, it is less likely to break when bent, which is preferable.
[0323] Furthermore, regarding another component of the flexible image display device, namely the second flexible image display device component, the tensile strength at 25°C as measured according to ASTM D882 is preferably 10 MPa or more, more preferably 15 MPa or more, particularly preferably 20 MPa or more, and preferably 900 MPa or less, more preferably 800 MPa or less, and particularly preferably 700 MPa or less.
[0324] If the tensile strength (ASTM D882) of another flexible image display device component is within the range described, it is preferred as it is less likely to break when bent.
[0325] Examples of components for the high tensile strength flexible image display device include polyimide film, polyester film, and aramid film, whose tensile strength is generally below 900 MPa.
[0326] On the other hand, as components of flexible image display devices with slightly lower tensile strength, examples include triacetyl cellulose (TAC) membranes and cyclic olefin polymer (COP) membranes, whose tensile strength is generally 10 MPa or higher.
[0327] Even if this flexible laminate is composed of flexible image display device components made of such a material with slightly lower tensile strength, it can suppress defects such as cracking through the action of this adhesive layer.
[0328] <Manufacturing Method of This Laminated Body>
[0329] There are no particular limitations on the manufacturing method of this laminate. As described above, for example, the resin composition can be coated onto the image display device component, preferably onto the flexible image display device component to form an adhesive layer. Alternatively, the adhesive layer can be pre-formed and then bonded to the image display device component, preferably to the flexible image display device component.
[0330] <<Image Display Devices>>
[0331] In one embodiment, the present invention is an image display device having the aforementioned laminate. (Hereinafter, it is sometimes referred to as "this image display device"). Examples of this image display device include those having a structure in which a laminate is combined with other image display device constituent components, the laminate having a structure in which two image display device constituent components are bonded together via the adhesive layer.
[0332] At this point, "other components constituting an image display device" may include, for example, FPC (Flexible Printed Circuit) cables, reflective sheets, light guide plates and light sources, diffusion films, prism sheets, liquid crystal panels, organic EL panels, anti-reflective films, color filters, polarizers, phase retardation plates, glass substrates, surface protective films, and components that integrate these components.
[0333] Specific examples of this image display device include: liquid crystal displays, organic EL displays, inorganic EL displays, electronic paper, plasma displays, and micro-electro-mechanical system (MEMS) displays used in personal computers, portable terminals, game consoles, televisions (TV), car navigation systems, touch panels, handwriting tablets, etc.
[0334] Flexible image display device
[0335] In one embodiment, the image display device is a flexible image display device (hereinafter sometimes referred to as "this flexible image display device"). A flexible image display device is an image display device assembled with a flexible image display device laminate, wherein the flexible image display device laminate has a structure in which two flexible image display device constituent members are bonded together via an adhesive layer. For example, by laminating a flexible image display device laminate having a structure in which two flexible image display device constituent members are bonded together via an adhesive layer onto other image display device constituent members, this flexible image display device having the laminate can be formed.
[0336] "Flexible image display device" refers to an image display device that does not leave any trace of bending even after repeated bending, can quickly return to its original state when the bending is removed, and can display images without distortion even when bent.
[0337] More specifically, an image display device can be described as being composed of a component capable of forming a fixed curved shape with a radius of curvature of 25 mm or more, and especially a component capable of withstanding repeated bending with a radius of curvature of less than 25 mm, more preferably less than 3 mm.
[0338] One of the features of this laminate is that it can prevent delamination and breakage even when folded in a high-temperature environment, and it also has good resilience, thus enabling the manufacture of flexible image display devices with excellent flexibility.
[0339] Example
[0340] The present invention will be further described in detail below with examples, but the present invention is not limited to the following examples as long as it does not deviate from its spirit.
[0341] <<Various Evaluation Criteria>>
[0342] The following evaluations were conducted using the adhesive layers with release films produced in the examples and comparative examples described later.
[0343] [Shear storage modulus (G') and glass transition temperature from -30℃ to 85℃]
[0344] The release film on one side of the adhesive layer with release film prepared in the examples and comparative examples was removed, and the layers were repeatedly stacked using a hand roller until the thickness was adjusted to about 0.8 mm. The resulting sample was then punched into a circle with a diameter of 8 mm. The sample was placed in a rheometer (T.A. Instruments "DHR-2") and dynamic viscoelasticity was measured under the following conditions: measuring fixture: 8 mm diameter parallel plate; frequency: 1 Hz; measuring temperature: -50 to 150 °C; heating rate: 5 °C / min. The values of shear storage modulus (G') and shear loss modulus (G") at -30 °C, -20 °C, 25 °C, 60 °C, and 85 °C were recorded.
[0345] Furthermore, the glass transition temperature (Tg) is determined based on the maximum value of Tanδ, which is defined by the ratio of shear storage modulus (G') to shear loss modulus (G").
[0346] [Adhesion to glass]
[0347] (Sample making)
[0348] A soda-lime glass plate is prepared and treated with atmospheric pressure plasma using a mixture of nitrogen and oxygen to make the water contact angle approximately 10°, thus serving as the substrate.
[0349] The release film on one side of the adhesive layer with release film prepared in the examples and comparative examples was removed, and a PET film (Made by MITSUBISHI CHEMICAL, S100, 50 μm thick) was applied as a backing film using a hand roller. This backing film was cut into strips 10 mm wide and 150 mm long, and the adhesive layer surface exposed after peeling off the residual release film was adhered to the surface of the substrate using a hand roller. The resulting laminate was subjected to autoclaving (60°C, gauge pressure 0.2 MPa, 20 minutes) and final bonding was performed to prepare samples for adhesive strength testing.
[0350] (Determination of adhesive strength)
[0351] For the obtained adhesive strength test sample, under the conditions of 23°C and 50%RH, the adhesive layer and the backing film were peeled off from the substrate together while being stretched at a peeling speed of 300 mm / min at an angle of 180°. The tensile strength (N / cm) was measured using a load sensor as the adhesive strength.
[0352] [Determination of PET adhesive strength]
[0353] In sample preparation, a PET film (MITSUBISHI CHEMICAL, S100, 50μm) that had been treated with atmospheric pressure plasma using a mixture of nitrogen and oxygen with a water contact angle of approximately 40° was used as the substrate. In addition, the adhesion to PET was measured in the same manner as the adhesion to glass.
[0354] [Recovery Rate]
[0355] The release film is removed from the adhesive layer with release film produced in the examples and comparative examples, and multiple adhesive layers are stacked to form a laminate with a thickness of 0.8 mm.
[0356] A cylinder with a diameter of 8 mm (height of 0.8 mm) was punched out from the obtained adhesive layer laminate and used as a sample.
[0357] For this sample, the recovery rate was determined using a viscoelasticity measuring apparatus (T.A. Instruments, “DHR 2”) under the following conditions.
[0358] That is, based on the strain (γ) after applying a pressure of 10 kPa at 25°C for 600 seconds. max(25) ) and then the strain (γ) after stress is unloaded and after 600 seconds min(25) The recovery rate is calculated using the following formula.
[0359] Recovery rate (%) = [(γ)] max(25) -γ min(25) ) / γ max(25) ]×100
[0360] [Gel fraction]
[0361] The release film was removed from the adhesive layer with the release film prepared in the examples and comparative examples, and approximately 0.1 g of the adhesive layer sheet was collected from the exposed adhesive layer. The collected adhesive layer sheet was wrapped in a pre-made bag-shaped SUS mesh (#150) of mass (X), and the bag opening was sealed to prepare a sample, and the mass (Y) of the sample was measured. The sample was then stored in the dark at 23°C for 24 hours while immersed in ethyl acetate. After that, the sample was removed and heated at 70°C for 4.5 hours to evaporate the ethyl acetate, and the mass (Z) of the dried sample was measured. The gel fraction was calculated for each of the measured masses according to the following formula.
[0362] Gel fraction (%) = [(ZX) / (YX)] × 100
[0363] [Bending Test]
[0364] (1) Room temperature dynamic bending test
[0365] Remove the release film from the adhesive layer with release film prepared in the examples and comparative examples, and roll-press a transparent polyimide (CPI) film (Kolon "C_50", 50 μm thick) and a PET film (MITSUBISHICHEMICAL "DIAFOIL S-100", 50 μm thick) onto the adhesive surface of the exposed adhesive layer to form a laminate of CPI film / adhesive layer / PET film. Then cut it into 40 mm × 100 mm pieces for evaluation samples for dynamic bending test.
[0366] The prepared evaluation sample was placed in a bending tester (YUASASYSTEM "DLDMLH-FS") with the CPI film as the inside, and a bending test was performed under the following test conditions at 23°C (room temperature).
[0367] • Test temperature: 23℃ (room temperature).
[0368] • Radius of curvature r: 1.5mm.
[0369] • Test speed: 60 rpm.
[0370] • Number of trials: 200,000.
[0371] The evaluation samples were visually observed after the test at 23℃ (normal temperature). The cases with creases on the adhesive layer and the cases with peeling observed at the interface between the adhesive and the bonded object were judged as "× (unacceptable)". The cases with no change observed were judged as "〇 (acceptable)".
[0372] (2) Static bending test under high temperature and high humidity
[0373] Remove the release film from the adhesive layer with release film prepared in the examples and comparative examples, and roll-press a transparent polyimide (CPI) film (Kolon "C_50", 50 μm thick) and a PET film (MITSUBISHICHEMICAL "DIAFOIL S-100", 50 μm thick) onto the adhesive surface of the exposed adhesive layer to form a laminate of CPI film / adhesive layer / PET film. Then cut it into 40 mm × 100 mm pieces for evaluation samples for static bending test.
[0374] The prepared evaluation sample was bent and fixed with the CPI film as the inside with a radius of curvature r: 2.0 mm. After being stored at 65°C and 90%RH for 24 hours, the clamp was opened and the resilience was evaluated after 1 hour.
[0375] For the evaluation samples after the visual observation test, regarding the anti-peeling properties, cases with creases on the adhesive layer and cases where peeling is observed at the interface between the adhered object and the adhesive layer will be judged as "× (unacceptable)", and cases with no change observed during visual observation will be judged as "〇 (acceptable)".
[0376] In addition, regarding resilience, cases where the inner angle of the bend is less than 30° are judged as "× (unacceptable)" and cases where the angle is greater than 30° are judged as "〇 (acceptable)".
[0377] Before implementing the examples, prepare the following raw materials.
[0378] <Polymer (A)>
[0379] Prepare copolymers containing the monomer components listed in Table 1 at ratios based on the parts by mass shown in Table 1. Table 1 shows the weight-average molecular weight of each polymer.
[0380] [Table 1]
[0381]
[0382] It should be noted that in Table 1, 2EHA refers to 2-ethylhexyl acrylate, BA refers to butyl acrylate, and HEA refers to 2-hydroxyethyl acrylate.
[0383] Prepare the following compounds as crosslinking agents (B), polymerization initiators (C), and other components.
[0384] <Crosslinking agent (B)>
[0385] • (B-1): Polytetramethylene glycol diacrylate (2-functional, manufactured by Shin-Nakamura Chemical Co., Ltd., “A-PTMG65”).
[0386] • (B-2): Carbamate acrylate (2-functional, Asia Industries, "SUA-008").
[0387] • (B-3): Trimethylolpropane triacrylate (3-functional, manufactured by Shin-Nakamura Chemical Co., Ltd., "TMPT").
[0388] • (B-4): Carbamate acrylate (6-functional, Asia Industries, "RUA-071").
[0389] • (B-5): Dipentaerythritol hexaacrylate (6-functional, manufactured by Nippon Kayaku Co., Ltd. as "DPHA").
[0390] <Polymerization Initiator (C)>
[0391] • (C-1): 2-hydroxy-2-methyl-1-phenyl-propane-1-one (a pyrolysis-type photoradical polymerization initiator, manufactured by IGM, "Omnirad 1173").
[0392] • (C-2): A mixture of 2,4,6-trimethylbenzophenone and 4-methylbenzophenone (hydrogen-extracting free radical polymerization initiator, "Esacure TZT" manufactured by IGM).
[0393] <Other (D)>
[0394] • (D-1): Monofunctional urethane acrylate (AGC "LD301").
[0395] • (D-2): Silane coupling agent (3-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Silicones, “KBM403”).
[0396] <Example 1>
[0397] A resin composition was prepared by uniformly mixing 1.5 parts by weight of crosslinking agent (B-5), 2.0 parts by weight of polymerization initiator (C-1), 25 parts by weight of monofunctional urethane acrylate (D-1), and 0.5 parts by weight of silane coupling agent (D-2) relative to 100 parts by weight of polymer (A-1).
[0398] Next, the resin composition is spread into a layer with a thickness of 50 μm on a 100 μm release film (PET film manufactured by MITSUBISHI CHEMICAL) after silicone demolding treatment. Furthermore, a 75 μm thick release film (PET film manufactured by MITSUBISHI CHEMICAL) after silicone demolding treatment is laminated on the layered resin composition.
[0399] Then, a high-pressure mercury lamp was used to accumulate a light intensity of 1000 mJ / cm². 2 In this manner, light with a wavelength of 365 nm is irradiated onto both surfaces of the layered resin composition through a release film to obtain an adhesive layer with a structure consisting of a release film, an adhesive layer, and another release film stacked sequentially.
[0400] <Examples 2 to 12 and Comparative Examples 1 to 4>
[0401] The proportions of each component and its mass fraction were set as described in Tables 2 and 3, except that in Example 11, the cumulative light intensity during irradiation was changed to 1300 mJ / cm. 2 In addition, an adhesive layer with a release film was made in the same manner as in Example 1.
[0402] [Table 2]
[0403]
[0404] [Table 3]
[0405]
[0406] [Physical Property Measurement / Evaluation]
[0407] The adhesive layers produced in the aforementioned examples / comparative examples were subjected to the various measurements and evaluations described above. The evaluation results of the adhesive layers are summarized in Tables 4 and 5.
[0408] [Table 4]
[0409]
[0410] [Table 5]
[0411]
[0412] It can be seen that the adhesive layers of Comparative Examples 1 to 3 have low gel fractions and insufficient curing degree.
[0413] The adhesive layer in Comparative Example 4 has an excessively high shear storage modulus (G') at 85°C.
[0414] The gel fraction and shear storage modulus (G') of the adhesive layer in Examples 1 to 12 are all within appropriate ranges.
[0415] Comparative Example 1 lacks shape stability and cannot be used for recovery rate testing.
[0416] Furthermore, it can be seen that the adhesive layers of Comparative Examples 2 and 3 exhibit very large maximum strain in the recovery rate test, failing to meet the shape retention requirement during bending.
[0417] Furthermore, the adhesive layers of Comparative Examples 1 to 3 all lacked resilience in static bending tests under high temperature and high humidity, and therefore cannot be considered suitable for applications such as foldable displays in high-temperature environments.
[0418] Furthermore, the adhesive layer of Comparative Example 4 lacked flexibility and adhesion to the PET substrate. In addition, peeling was confirmed in the static bending test under high temperature and high humidity, and the recovery was also insufficient.
[0419] Any of the adhesive layers in Examples 1 to 12 showed appropriate adhesion to both glass and PET substrates.
[0420] Furthermore, in the recovery test, the maximum strain was within an appropriate range, and the recovery rate was above 70%, which is good.
[0421] Furthermore, it showed good results in both dynamic bending tests at room temperature and static bending tests under high temperature and humidity, indicating that it can withstand harsh environments and repeated or prolonged bending, and possesses the high durability required for applications such as rollable panels and foldable panels.
[0422] As shown above, according to the present invention, it is possible to provide adhesive layers with excellent bending adaptability and good cohesion and / or adhesion, adhesive layers with release films, laminates, image display devices, and adhesive layers for components constituting image display devices.
[0423] The above embodiments illustrate specific aspects of the present invention, but these embodiments are merely examples and not intended to be limiting. It is intended that various modifications, obvious to those skilled in the art, fall within the scope of the present invention.
[0424] Industrial availability
[0425] The adhesive layer of the present invention exhibits excellent flexibility and good cohesion and / or adhesion. Therefore, it is suitable for use as an adhesive layer in image display devices.
Claims
1. An adhesive layer for a component of a flexible image display device, which satisfies the following necessary conditions [I] to [V], The adhesive layer for the components of the flexible image display device is formed from a resin composition comprising a polymer (A), a crosslinking agent (B), and a polymerization initiator (C). The polymer (A) comprises a copolymer formed of a monomeric component comprising at least 50% by mass of a compound containing a (meth)acryloyl group. The crosslinking agent (B) comprises a crosslinking agent with three or more functional groups. The polymerization initiator (C) comprises a pyrolysis-type photopolymerization initiator. [I] The shear storage modulus at -20℃, i.e., G' at -20℃, is below 300 kPa. [II] The shear storage modulus at 85℃, i.e., G' at 85℃, is above 5.0 kPa and below 30 kPa. [III] Gel fraction of 45% or higher and 95% or lower. [IV] The adhesion strength relative to the polyethylene terephthalate substrate is 5.0 N / cm or more at 23°C. [V] Based on the maximum strain γ after applying a pressure of 10 kPa for 600 seconds with a thickness of 0.5–1.2 mm at 25°C. max(25) And then the strain γ after stress relief and 600 seconds min(25) The recovery rate calculated using the following formula is over 70%. Recovery rate % = [(γ)] max(25) -γ min(25) ) / γ max(25) 〕×100.
2. The adhesive layer for the constituent components of the flexible image display device according to claim 1, wherein, The adhesive layer used for the components of the flexible image display device has an adhesion force of 4.5 N / cm or more relative to the glass substrate at 23°C.
3. The adhesive layer for the constituent components of the flexible image display device according to claim 1, wherein, The flexible image display device uses an adhesive layer with a thickness of 0.5–1.2 mm, and the maximum strain γ is measured after applying a pressure of 10 kPa for 600 seconds at 25°C. max(25) It is below 600%.
4. The adhesive layer for the constituent components of the flexible image display device according to claim 1, wherein, The glass transition temperature Tg of the adhesive layer used to construct the flexible image display device, defined by the maximum value of Tanδ obtained through dynamic viscoelasticity measurement in a shear mode at a frequency of 1 Hz, is below -15°C.
5. An adhesive layer for a flexible image display device component with a release film, the adhesive layer for a flexible image display device component having one or more release films and a laminated structure of the adhesive layer for a flexible image display device component according to any one of claims 1 to 4.
6. A laminate comprising one or more components for an image display device and an adhesive layer for constituting a flexible image display device according to any one of claims 1 to 4.
7. A laminate comprising two image display device constituent members and an adhesive layer for a flexible image display device constituent member disposed between the two image display device constituent members according to any one of claims 1 to 4.
8. The laminate according to claim 7, wherein, One of the components of the two image display devices is a surface protection panel, and the other is a component consisting of any one or any combination of two or more of the following: a touch sensor film, an image display panel, a color filter, a polarizing element, and a phase difference film.
9. An image display device comprising a laminate according to claim 6.
10. The image display device according to claim 9, wherein, The image display device is a flexible image display device.
Citation Information
Patent Citations
Polyester film and use of the same
JP2020196255A
Double-sided pressure-sensitive adhesive sheet, laminate comprising component member for image display device, kit for laminate formation, and use of double-sided pressure-sensitive adhesive sheet
WO2018173896A1